Resin film, metal layer-integrated resin film, and film capacitor
By using a resin film with a controlled product of volume resistivity and dielectric constant, the resin film addresses the issue of insulation resistance decline in capacitors, ensuring long-term reliability and performance.
Patent Information
- Application Number
- JP2024069529
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-10-26
- Filing Date
- 2024-04-23
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2038-10-31
AI Technical Summary
Existing capacitor technologies fail to accurately predict long-term reliability due to insufficient evaluation of insulation resistance decline during life tests, leading to premature performance deterioration.
A resin film with a specific product of volume resistivity and relative dielectric constant, measured under controlled potential gradients, is used to suppress insulation resistance decline, ensuring long-term reliability by correlating these properties with capacitor element performance.
The resin film effectively suppresses insulation resistance decline, ensuring capacitors maintain performance over extended periods, even under high temperatures, by accurately measuring and setting the product of volume resistivity and dielectric constant to predetermined values.
Smart Images

Figure 0007615514000001 
Figure 0007615514000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin film, a metal layer-integrated resin film, and a film capacitor. [Background technology]
[0002] Polypropylene films have excellent electrical properties such as high voltage resistance and low dielectric loss, and also have high moisture resistance. Therefore, they are widely used in electronic devices and electrical devices. Specifically, they are used as films for high-voltage capacitors, various switching power supplies, filter capacitors (e.g., converters, inverters, etc.), smoothing capacitors, etc.
[0003] In recent years, there has been a demand for smaller capacitors with higher capacitance. In order to improve the capacitance without changing the volume of the capacitor, it is preferable to make the film thinner as a dielectric. Therefore, there is a demand for thinner films.
[0004] Furthermore, in recent years, polypropylene films have begun to be widely used as capacitors for inverter power supply devices that control drive motors in electric vehicles, hybrid vehicles, etc. Capacitors for inverter power supply devices used in automobiles, etc. are required to be small, lightweight, and have high capacity, as well as to have high voltage resistance over a wide temperature range (e.g., -40°C to 90°C) for a long period of time.
[0005] In Patent Document 1, the volume resistivity at 110°C is 5×10 14 The description states that the polypropylene film has a volume resistivity of 5×10 Ω·cm or more at 110°C (see claim 5). 14It is stated that if the resistance is less than Ω·cm, the reliability may be impaired (see paragraph
[0028] ). It is also stated that the reliability was evaluated by dismantling the capacitor element and examining the state of breakdown (paragraph
[0147] ). Specifically, the voltage was gradually increased in steps of 50 VDC / 1 min, and the voltage was increased until the capacitance decreased to 10% or less of the initial value, and then whether or not a breakthrough was observed was evaluated (paragraphs
[0141] ,
[0147] -
[0151] ). In general, indicators of electrical insulation can be roughly divided into "breakdown" that occurs when a voltage is applied and "insulation deterioration" that gradually progresses by applying a voltage for a long time. In Patent Document 1, since the evaluation is performed by applying a high voltage for a short time, it is considered that the breakthrough indicates a breakthrough, and it is considered that the former characteristic is good. In other words, it is believed that Patent Document 1 describes that when the volume resistivity at 110°C is set to a certain value or higher, penetrating dielectric breakdown is suppressed and short-term dielectric strength is good. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2016 / 182003 Summary of the Invention [Problem to be solved by the invention]
[0007] On the other hand, while studying a capacitor with high reliability that can withstand long-term use, the present inventors have found that, for example, even if a decrease in capacitance can be suppressed in a 1000-hour life test, it does not necessarily mean that the capacitor can withstand long-term use. In other words, since it is impossible to perform a life test of a capacitor under the same conditions as the actual use conditions and for the same time as in actual use, a load is applied that is somewhat higher than the actual use conditions, and the measurement is stopped at a time (for example, 1000 hours) shorter than the actually assumed durability time, and whether the capacitor can withstand long-term use is determined based on the evaluation at this point. However, the inventors have found that even if a decrease in capacitance can be suppressed in a 1000-hour life test, it does not necessarily mean that the capacitor can withstand long-term use.
[0008] The present inventors have conducted intensive research into the above findings. As a result, they have found that a highly reliable capacitor capable of withstanding long-term use can be obtained by suppressing the rate of decrease in the insulation resistance value (IR) of a capacitor element in a life test. More specifically, they have noticed that, for example, even if the decrease in the capacitance of a capacitor element can be suppressed in a life test, the insulation resistance value (IR) of the capacitor element may be significantly decreased compared to the initial value. In such a case, if the test is continued after that, the amount of heat generated increases due to the decrease in the insulation resistance value (IR) of the capacitor element, and the capacitance of the capacitor element decreases exponentially, resulting in a rapid decrease in performance. In other words, the present inventors thought that the decrease in the capacitance of a capacitor element in a life test is an evaluation of the degree of deterioration during the life test period, and it cannot be said that it can be clearly understood how the performance will be after the life test. On the other hand, they thought that the decrease (decrease rate) of the insulation resistance value (IR) of a capacitor element is an index that can evaluate the degree of deterioration during the life test period, and at the same time, it is an index that can evaluate the degree of deterioration progress after the life test. In other words, if the rate of decline in the insulation resistance (IR) of a capacitor element is large during the life test period, continuing the test thereafter will result in a rapid decline in performance, such as an exponential decline in capacitance, and so on. Therefore, it was thought that IR can also be used as an index to evaluate the degree of degradation after the life test.
[0009] However, it was unclear how to suppress the decrease in insulation resistance (IR) during the life test of a capacitor element.
[0010] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a resin film capable of suppressing the rate of decrease in insulation resistance (IR) of a capacitor element in a life test. The present invention also provides a metal layer-integrated resin film having the resin film, and a film capacitor having the metal layer-integrated resin film. [Means for solving the problem]
[0011] The present inventors have conducted extensive research into this issue and have surprisingly found that the rate of decrease in insulation resistance (IR) of a capacitor element during a life test can be suppressed by setting the product of the volume resistivity and the relative dielectric constant of a resin film to a predetermined value or more, thereby completing the present invention.
[0012] In the past, it was generally thought that in life tests of capacitor elements, if the decrease in capacitance was suppressed, the capacitor's performance could be evaluated as being satisfactory. As for insulation resistance (IR), if the initial value was satisfactory, no detailed examination was conducted of the rate of subsequent decrease.
[0013] Furthermore, as described above, Patent Document 1 appears to describe that when the volume resistivity of the film at 110°C is set to a predetermined value or higher, it is possible to suppress the decrease in capacitance of the capacitor element and to prevent short-term insulation breakdown when a high voltage is applied. However, there is no description of the ability to suppress the rate of decrease in the insulation resistance value (IR) of the capacitor element in a life test by setting the volume resistivity value of the film or the product of the volume resistivity and dielectric constant to a predetermined value or higher.
[0014] In addition, the method for measuring the volume resistivity of the film in Patent Document 1 is different from the method for measuring the volume resistivity of the film of the present invention, as will be described in detail later. Furthermore, the method for measuring the volume resistivity in Patent Document 1 does not allow a correlation to be obtained between the volume resistivity value and the rate of decrease in the insulation resistance value (IR) of a capacitor element during a life test. Therefore, even if a resin film having a volume resistivity equal to or higher than a predetermined value is obtained by the method for measuring the volume resistivity in Patent Document 1, this does not mean that the resin film can suppress the rate of decrease in the insulation resistance value (IR) of a capacitor element during a life test.
[0015] The resin film according to the present invention is Contains crystalline thermoplastic resin as the main component, Volume resistivity ρ at 23°C measured by the following measurement method (1) V23℃and the relative dielectric constant ε at 23°C measured by the following measurement method (2) r23℃ The product of [ρ V23℃ ×ε r23℃ ], but 1×10 16 Ω cm or more, Volume resistivity ρ at 100°C measured by the following measurement method (3) V100℃ and the relative dielectric constant ε at 100°C measured by the following measurement method (4) r100℃ The product of [ρ V100℃ ×ε r100℃ ], but 1×10 14 It is characterized by a resistance of Ω·cm or more. <Measurement method> (1) Apply a voltage so that the potential gradient is 200 V / μm in an atmosphere of 23°C, and calculate from the current value after 1 minute using the following formula. ρ V23℃ = [(effective electrode area) × (applied voltage)] / [(resin film thickness) × (current value)] (2) Apply conductive paste to both sides of the resin film and dry to form electrodes. Attach wires to the electrodes using conductive paste. Measure the capacitance C of the resulting test capacitor in an atmosphere of 23°C and calculate ε using the following formula. r23℃ Calculate. (capacity C)=(ε r23℃ ) × (dielectric constant of vacuum ε0) × [(electrode area) / (resin film thickness)] (3) Apply a voltage so that the potential gradient is 200 V / μm in an atmosphere of 100°C, and calculate from the current value after 1 minute using the following formula. ρ V100℃ = [(effective electrode area) × (applied voltage)] / [(resin film thickness) × (current value)] (4) Apply conductive paste to both sides of the resin film and dry to form electrodes. Attach wires to the electrodes using conductive paste. Measure the capacitance C of the resulting test capacitor in an atmosphere of 100°C and calculate ε using the following formula. r100℃ Calculate. (capacity C)=(ε r100℃ ) × (dielectric constant of vacuum ε0) × [(electrode area) / (resin film thickness)]
[0016] Conventionally, in the general method of measuring the volume resistivity of a film, the number of digits is a reliable value for the accuracy of the measured value, and values more precise than the number of digits are considered to be within the margin of error. However, the volume resistivity of a film measured with an accuracy of the number of digits does not provide a clear correlation with the rate of decrease in insulation resistance (IR) in a life test of a capacitor element made from the film. On the other hand, in the present invention, the volume resistivity ρ V23℃ is the volume resistivity ρ at 100°C measured by the above measurement method (1). V100℃ is measured by the above-mentioned measurement method (3). This allows the volume resistivity of the film to be obtained with higher accuracy than the order of magnitude level. In the method for measuring the volume resistivity in the present invention, one of the reasons for the improved accuracy is that the potential gradient is constant (200 V / μm in the present invention). Generally, within the range where Ohm's law holds, the volume resistivity will be constant regardless of the voltage at which it is measured (whatever the potential gradient). However, in areas where Ohm's law does not hold (high electric field areas), the volume resistivity will vary depending on the voltage at which it is measured. Specifically, the higher the voltage at which it is measured (the higher the potential gradient), the lower the measured volume resistivity will be. For this reason, it is important to compare the volume resistivity of films under conditions where the potential gradient is the same. In the present invention, since the volume resistivity is calculated with the potential gradient constant, for example, when the volume resistivity of a plurality of types of films is measured, it is possible to determine that the values that would have been evaluated as being almost the same volume resistivity in the conventional method because the values are the same digits are clearly different values. As can be seen from the examples, there is a good correlation between the volume resistivity of the film obtained by the volume resistivity measurement method of the present invention and the rate of decrease in the insulation resistance value (IR) of the capacitor element in the life test. The relative dielectric constant is a value specific to the molecular structure and crystal form of the resin film. Therefore, the product of the volume resistivity and the relative dielectric constant in the present invention also has a good correlation with the rate of decrease in the insulation resistance value (IR) in the life test. From the above, the higher the volume resistivity of the film of the present invention, the more suppressed the rate of decrease in the insulation resistance (IR) of the capacitor element in a life test. And the product [ρ V23℃ ×ε r23℃ ], but 1×10 16 If the resistance is Ω·cm or more, it can withstand actual long-term use in an atmosphere of 23°C (room temperature). In addition, the product [ρ V100℃ ×ε r100℃ ], but 1×10 14 If the resistance is Ω·cm or more, it can withstand actual long-term use in an atmosphere of 100°C (high temperature). In addition, the product [ρ V23℃ ×ε r23℃ ], but 1×10 16 If the dielectric constant is Ω·cm or more, it can withstand actual long-term use in an atmosphere of 23°C (normal temperature), and the product [ρ V100℃ ×ε r100℃ ], but 1×10 14 The reason why it is said that a resistance of Ω·cm or more means that the material can withstand long-term actual use in an atmosphere at 100°C (high temperature) is that this value is set as the evaluation standard for life tests, and it is assumed that if the value is above this value, there is an extremely high possibility that the material will be able to withstand long-term actual use.
[0017] In the present invention, the volume resistivity ρ V23℃ Instead, volume resistivity ρ V23℃ and relative dielectric constant ε r23℃ The product of [ρ V23℃ ×ε r23℃ ], 1×10 16 The reason why the resistance is set to Ω·cm or more is as follows. As described above, the higher the volume resistivity of the film of the present invention, the more suppressed the rate of decrease in the insulation resistance (IR) of the capacitor element during the life test. Therefore, the higher the volume resistivity, the more preferable it is. On the other hand, the larger the dielectric constant, the greater the ability to store electricity. In other words, if the electrode area is the same, the larger the dielectric constant, the greater the capacitance of the capacitor. Therefore, the higher the dielectric constant, the more preferable it is. When examining resin materials, there are various materials, such as those having a relatively large volume resistivity but a relatively small relative dielectric constant, and those having a relatively small volume resistivity but a relatively large relative dielectric constant. When considering various such materials, it is expected that those with a relatively large volume resistivity of the film will have a low leakage current of the capacitor element during the life test period, and as a result, the heat generated by the capacitor element will be suppressed, and the deterioration rate will be slower. Therefore, even if the dielectric constant is relatively small, it is believed that the performance will be sufficient for long-term actual use. Conversely, for films with a relatively small volume resistivity, the insulation resistance (IR) of the capacitor element is more likely to decrease than for those with a relatively large volume resistivity, and the rate of deterioration is expected to be somewhat faster. However, when the relative dielectric constant is relatively large, the ability to store electricity is originally high. Therefore, (A) the film area (electrode area) required to obtain the desired capacitance can be reduced, or (B) the film thickness can be increased while maintaining the film area. As a result, the leakage current of the capacitor element during the life test period can be reduced, and heat generation can be suppressed. This point will be explained in more detail. Assume that capacitor elements with the same capacitance are fabricated using films with different dielectric constants. In this case, using a film with a relatively large dielectric constant is advantageous in that it allows a choice from the following three options (1) to (3) to achieve a reduction in leakage current. (1) Reduce the area of the film used while maintaining the same thickness. (2) Make the film thicker without changing the film area. (3) Taking the advantages of the previous two, make the film slightly thicker and the film area slightly smaller. As a result, the decrease in insulation resistance (IR) of the capacitor element is further suppressed, and it is believed that the element will be able to withstand actual long-term use. Therefore, the product of the volume resistivity and the relative dielectric constant is used as an index of whether or not a material can withstand actual long-term use.
[0018] As described above, the dielectric constant is a value specific to the molecular structure (conformation and packing) of a resin film, but it was difficult to accurately measure the dielectric constant of a thin film using conventional methods for measuring the dielectric constant. On the other hand, in the present invention, the relative dielectric constant ε r23℃ is measured by the above measurement method (2), and the relative dielectric constant ε at 100°C is r100℃ is measured by the above-mentioned measurement method (4). This makes it possible to measure the relative dielectric constant of even a thin resin film simply and with good reproducibility. From the above, the product [ρ V23℃ ×ε r23℃ ] and the product [ρ V100℃ ×ε r100℃ ] values, more accurate values can be obtained. As a result, a more accurate value can be obtained as an indicator of whether the material can withstand actual long-term use.
[0019] In Patent Document 1, a voltage of 100V is applied for 1 minute, and the volume resistivity is calculated from the volume resistance value at the time when 1 minute has elapsed (see paragraph
[0137] ). The film thickness is not taken into consideration when applying the voltage. For example, the film of Example 8 has a thickness of 2.3 μm and a potential gradient of about 43.5 V / μm (100 V / 2.3 μm). On the other hand, the film of Example 9 has a thickness of 5.8 μm and a potential gradient of about 17.2 V / μm (100 V / 5.8 μm). As described above, in the region where Ohm's law does not hold (high electric field region), the volume resistivity differs depending on the voltage at the time of measurement, so it must be said that the measurement method of volume resistivity as in Patent Document 1 has low accuracy. Therefore, even if the volume resistivity is measured by the method of Patent Document 1, it is not possible to obtain a clear correlation with the rate of decrease in the insulation resistance (IR) of the capacitor element during a life test. First of all, in Patent Document 1, the purpose of the volume resistivity is to suppress the penetration damage of the film when a high voltage is applied and to ensure good initial characteristics, and is not intended to evaluate the quality of the capacitor element in long-term use. Therefore, it must be said that Patent Document 1 does not provide any motivation to use the volume resistivity value to evaluate the capacitor element's ability to withstand long-term use.
[0020] In this specification, the term "life test" refers to an accelerated test in which a capacitor element is deteriorated under conditions of temperature and voltage that are more severe than those of actual use. The measurement is stopped after a period of time (e.g., 1,000 hours) that is shorter than the expected service life, and the element is evaluated based on the evaluation at this point to determine whether it can withstand long-term use.
[0021] Furthermore, the resin film according to the present invention has a product [ρ V23℃ ×ε r23℃ ], but 1×10 16 Ω·cm or more and the product [ρ V100℃ ×ε r100℃ ], but 1×10 14 Since the dielectric constant is Ω·cm or more, and the decrease in the insulation resistance (IR) of the capacitor element is suppressed, the decrease in capacitance C is also suppressed. As a result, the decrease in (C·IR) is also suppressed. It is generally known that the larger the capacitance C of a capacitor (for example, the larger the electrode area, the thinner the dielectric), the smaller the insulation resistance (IR) (the easier it is for current to leak). In general, the "CR product (capacitance x insulation resistance)" is used as an index to fairly compare capacitors even if their capacitance C is different. In this specification, (C IR) is synonymous with this CR product, and has the advantage that it allows for a fair comparison of capacitors even if their capacitance C is different.
[0022] The resin film having the above structure preferably has a thickness within a range of 0.8 to 6 μm.
[0023] If the thickness is 6 μm or less, the decrease in capacitance can be further suppressed. In addition, since the decrease in capacitance can be further suppressed, the decrease rate (%) of (C·IR) can also be further suppressed. In addition, when the thickness of the resin film is 6 μm or less, the capacitance per unit volume can be increased when the film is made into a capacitor element, so that the film can be suitably used for a capacitor. In addition, when the thickness of the resin film is 0.8 μm or more, it is preferable from the viewpoint of film formation stability.
[0024] The resin film having the above structure is preferably used for a capacitor.
[0025] Product [ρ V23℃ ×ε r23℃ ] and the product [ρ V100℃ ×ε r100℃ The resin film having a value of at least a predetermined value is preferably used for a capacitor because the rate of decrease in insulation resistance (IR) in a life test of a capacitor element is suppressed.
[0026] The resin film having the above structure is preferably biaxially stretched.
[0027] When it is biaxially stretched, the product [ρ V23℃ ×ε r23℃ ] and the product [ρ V100℃ ×ε r100℃ ] is a predetermined value or more.
[0028] The resin film having the above structure preferably has a thickness within a range of 0.8 to 22 μm.
[0029] If the thickness is within the range of 0.8 to 22 μm, the capacitance can be increased, making it suitable for use in a capacitor.
[0030] In the resin film having the above configuration, the crystalline thermoplastic resin preferably satisfies at least one of the following: (a) the main chain is an aliphatic hydrocarbon; (b) the main chain has an amide bond; and (c) the main chain has an ether bond.
[0031] A crystalline thermoplastic resin that satisfies at least one of the following conditions has a relatively high melting point: (a) the main chain is an aliphatic hydrocarbon, (b) the main chain has an amide bond, and (c) the main chain has an ether bond. Therefore, when the crystalline thermoplastic resin satisfies at least one of the above conditions (a) to (c), it has excellent heat resistance.
[0032] In the resin film having the above structure, it is also preferable that at least one hydrogen atom is bonded to each of the carbon atoms constituting the main chain of the crystalline thermoplastic resin.
[0033] When at least one hydrogen atom is bonded to each of the carbon atoms constituting the main chain of the crystalline thermoplastic resin, the resin is suitable as a dielectric. For example, when only chlorine atoms or fluorine atoms are bonded to the carbon atoms constituting the main chain, and no hydrogen atoms are bonded, the resin may become a ferroelectric, and there is a concern that the film may be deformed (distorted) due to the inverse piezoelectric effect when a voltage is applied. However, even if the resin is a ferroelectric, it is not impossible to use the resin for a capacitor.
[0034] In the resin film having the above structure, the product [ρ V23℃ ×ε r23℃ ], but 1×10 16 Ω cm or more, The product [ρ V100℃ ×ε r100℃ ], but 1×10 14 Ω cm or more, The relative dielectric constant ε r100℃ is preferably 2 or more and 5 or less.
[0035] The product [ρ V23℃ ×ε r23℃ ], but 1×10 16 Ω·cm or more, and the product [ρ V100℃ ×ε r100℃ ], but 1×10 14 Ω·cm or more, and the relative dielectric constant ε r100℃ When the ratio is 2 or more and 5 or less, the rate of decrease in the insulation resistance (IR) of the capacitor element in a life test is further suppressed.
[0036] In the resin film having the above structure, log 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃ )] is preferably 5 or less.
[0037] The log 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃ When the log )] is 5 or less, it can be said that the difference in the rate of decrease in insulation resistance (IR) in the life test is small between 23°C (normal temperature) and 100°C (high temperature). 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃ ) can be used as an index of heat resistance, and if this index is 5 or less, it can be said that the heat resistance is superior.
[0038] In the resin film having the above configuration, the crystalline thermoplastic resin is preferably a polypropylene resin.
[0039] Since polypropylene resin has a relatively high volume resistivity, when the crystalline thermoplastic resin is polypropylene resin, the rate of decrease in the insulation resistance (IR) of the capacitor element during a life test can be suitably suppressed.
[0040] The ash content in the resin constituting the resin film is preferably 5 ppm or more and 35 ppm or less.
[0041] When the ash content in the resin (raw resin) constituting the resin film is 5 ppm or more and 35 ppm or less, the generation of low molecular weight components having polarity can be suppressed and the electrical properties as a capacitor can be improved.
[0042] In the resin film having the above structure, the heptane insoluble content is preferably 96% or more and 99.5% or less.
[0043] The higher the heptane insoluble content, the higher the stereoregularity of the resin. When the heptane insoluble content (HI) of the resin film is 96% or more and 99.5% or less, the moderately high stereoregularity leads to a moderate improvement in the crystallinity of the resin, and the voltage resistance at high temperatures is improved. On the other hand, the solidification (crystallization) speed during cast raw sheet molding becomes moderate, and the film has moderate extensibility.
[0044] In the resin film having the above structure, it is preferable that the molecular weight distribution [(weight average molecular weight Mw) / (number average molecular weight Mn)] is 5 or more and 12 or less.
[0045] When the molecular weight distribution [(weight average molecular weight Mw) / (number average molecular weight Mn)] of the resin film is within the above range, appropriate resin fluidity is obtained during biaxial stretching, and it is easy to obtain an extremely thin biaxially stretched polypropylene film with no thickness unevenness. In addition, by adjusting the distribution of high molecular weight and low molecular weight components, the voltage resistance of a capacitor constructed using the biaxially stretched resin film can be further improved.
[0046] In the resin film having the above structure, the crystallite size calculated from the half-width of the reflection peak of the α-crystal (040) plane measured by wide-angle X-ray diffraction using the Scherrer formula is preferably 9 nm or more and 15 nm or less.
[0047] When the crystallite size of the resin film is 15 nm or less, the leakage current is small and the voltage resistance at room temperature and high temperature is preferably improved, whereas when the crystallite size is 9 nm or more, it is preferable from the viewpoint of maintaining the mechanical strength and melting point of the resin film (particularly, polypropylene film).
[0048] In the resin film having the above structure, the plane orientation coefficient is preferably 0.010 to 0.016.
[0049] It is preferable that the plane orientation coefficient of the resin film is within the above range, since this can further reduce dielectric breakdown under high temperature and high voltage conditions.
[0050] In the resin film having the above structure, the melting point is preferably 170° C. or higher and 176° C. or lower.
[0051] When the melting point of the resin film is 170° C. or higher, the voltage resistance and thermal dimensional stability at high temperatures are excellent, whereas when the melting point is 176° C. or lower, the rigidity of the film becomes appropriate, and it is easy to form the film into a stretched film.
[0052] In the resin film having the above structure, it is preferable that the melting enthalpy is 90 J / g or more and 125 J / g or less.
[0053] The melting enthalpy of the resin film is preferably 90 J / g or more since the crystallites are strong, whereas the melting enthalpy of the resin film is preferably 125 J / g or less since the crystallite size is appropriately small.
[0054] The metal layer-integrated resin film according to the present invention is The resin film; and a metal layer laminated on one or both sides of the resin film.
[0055] According to the above-mentioned configuration, since the resin film has a metal layer laminated on one or both sides thereof, the film can be used for a film capacitor in which the resin film serves as a dielectric and the metal layer serves as an electrode. V23℃ ×ε r23℃ ], but 1×10 16 Ω·cm or more, and the product [ρ V100℃ ×ε r100℃ ], but 1×10 14 The resin film has a resistance of Ω·cm or more, so the rate of decrease in the insulation resistance (IR) of the capacitor element during a life test is suppressed.
[0056] The film capacitor according to the present invention is characterized in that it has the metal layer-integrated resin film that is wound, or has a configuration in which a plurality of the metal layer-integrated resin films are laminated. Effect of the Invention
[0057] According to the present invention, it is possible to provide a resin film capable of suppressing the rate of decrease in insulation resistance (IR) of a capacitor element in a life test, and a metal layer-integrated resin film having the resin film, and a film capacitor having the metal layer-integrated resin film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0058] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0059] In this specification, the expressions "contain" and "include" include the concepts of "contain", "include", "consist essentially of", and "consist only of".
[0060] In this specification, the terms "element," "capacitor," "capacitor element," and "film capacitor" mean the same thing.
[0061] The resin film according to this embodiment is Contains crystalline thermoplastic resin as the main component, Volume resistivity ρ at 23°C measured by the following measurement method (1) V23℃ and the relative dielectric constant ε at 23°C measured by the following measurement method (2) r23℃ The product of [ρ V23℃ ×ε r23℃ ], but 1×10 16 Ω cm or more, Volume resistivity ρ at 100°C measured by the following measurement method (3) V100℃ and the relative dielectric constant ε at 100°C measured by the following measurement method (4) r100℃ The product of [ρ V100℃ ×ε r100℃ ], but 1×1014 Ω·cm or more. <Measurement method> (1) Apply a voltage so that the potential gradient is 200 V / μm in an atmosphere of 23°C, and calculate from the current value after 1 minute using the following formula. ρ V23℃ = [(effective electrode area) × (applied voltage)] / [(resin film thickness) × (current value)] (2) Apply conductive paste to both sides of the resin film and dry to form electrodes. Attach wires to the electrodes using conductive paste. Measure the capacitance C of the resulting test capacitor in an atmosphere of 23°C and calculate ε using the following formula. r23℃ Calculate. (capacity C)=(ε r23℃ ) × (dielectric constant of vacuum ε0) × [(electrode area) / (resin film thickness)] (3) Apply a voltage so that the potential gradient is 200 V / μm in an atmosphere of 100°C, and calculate from the current value after 1 minute using the following formula. ρ V100℃ = [(effective electrode area) × (applied voltage)] / [(resin film thickness) × (current value)] (4) Apply conductive paste to both sides of the resin film and dry to form electrodes. Attach wires to the electrodes using conductive paste. Measure the capacitance C of the resulting test capacitor in an atmosphere of 100°C and calculate ε using the following formula. r100℃ Calculate. (capacity C)=(ε r100℃ ) × (dielectric constant of vacuum ε0) × [(electrode area) / (resin film thickness)]
[0062] The above measurement method (1) will be described in detail. In the following description, unless otherwise specified, the measurement conditions are in accordance with JIS C 2139. First, a jig for measuring volume resistivity (hereinafter, simply referred to as a "jig") is placed in a thermostatic chamber at 23° C. The jig for measuring volume resistivity has the following configuration. A DC power source and a DC ammeter are connected to each electrode of the jig. <Volume resistivity measurement jig> Main electrode (50mm diameter) Counter electrode (diameter 85 mm) A ring-shaped guard electrode (outer diameter 80 mm, inner diameter 70 mm) surrounding the main electrode Each electrode is made of gold-plated copper, and conductive rubber is attached to the surface that comes into contact with the sample. The conductive rubber used is EC-60BL (W300) manufactured by Shin-Etsu Silicone Co., Ltd., and is attached so that the glossy side of the conductive rubber comes into contact with the gold-plated copper.
[0063] Next, the resin film (hereinafter also referred to as the sample) is placed in an environment of 23°C and 50% RH for 24 hours. After that, the sample is set in a jig in a thermostatic chamber. Specifically, the main electrode and guard electrode are attached to one side of the sample, and the counter electrode is attached to the other side, and the sample and each electrode are attached with a load of 5 kgf. Then, it is left to stand for 30 minutes.
[0064] Next, a voltage is applied to the sample so that the potential gradient is 200 V / μm.
[0065] After applying the voltage, the current value is read one minute later, and the volume resistivity is calculated using the following formula: The voltage is applied using a Keithley 2290-10 (DC power source), and the current value is measured using a Keithley 2635B (DC ammeter). Volume resistivity = [(effective electrode area) x (applied voltage)] / [(sample thickness) x (current value)]
[0066] Here, the effective electrode area is calculated by the following formula. (Effective electrode area) = π × [[[(main electrode diameter) + (guard electrode inner diameter)] / 2] / 2] 2
[0067] In this embodiment, the effective electrode area is not the area of the main electrode, but the area of the space between the main electrode and the guard electrode that is the same distance from the main electrode or closer than the main electrode, thereby enabling more accurate measurement of the current value.
[0068] The measurement method (1) has been described above.
[0069] Next, the above measurement method (2) will be described in detail. First, a 30 mm diameter form is placed on one side of a resin film (hereafter also referred to as the sample) and a conductive paste is applied. After the solvent has sufficiently volatilized and the conductive paste no longer flows even when the form is removed, the form is removed and the sample is left for half a day. This forms an electrode. Next, an electrode is formed in the same manner on the other side of the sample, sandwiching the film between the two so that it overlaps with the previous electrode. This results in a capacitor with electrodes of 30 mm diameter on each side.
[0070] To connect the prepared capacitor to a measuring device, wires are connected to each electrode of the capacitor with conductive paste. If the wires face each other with the film in between, capacitance will also be formed at the wires, so the wires are connected as far apart as possible. The wires are not particularly limited, but may be tin-plated copper.
[0071] Next, each lead is connected to a measuring device to measure the capacitance C of the capacitor. The measurement is performed under the following conditions after leaving the capacitor for 30 minutes in a thermostatic chamber set at 23°C. <Measurement conditions> Applied voltage: 1V Measurement frequency: 1kHz
[0072] Then, the relative dielectric constant ε r23℃ Calculate. (capacity C)=(ε r23℃ ) × (dielectric constant of vacuum ε0) × [(electrode area) / (resin film thickness)]
[0073] The measurement method (2) has been explained above.
[0074] Details of the measurement method (3) are the same as those of the measurement method (1) except that the temperature of the thermostatic bath is set to 100° C. Therefore, detailed explanations are omitted here.
[0075] Details of the measurement method (4) are the same as those of the measurement method (2) except that the temperature of the thermostatic bath is set to 100° C. Therefore, detailed explanations will be omitted here.
[0076] Conventionally, in the general method of measuring the volume resistivity of a film, the number of digits is a reliable value for the accuracy of the measured value, and values more precise than the number of digits are considered to be within the margin of error. However, the volume resistivity of a film measured with an accuracy of the number of digits does not provide a clear correlation with the rate of decrease in insulation resistance (IR) in a life test of a capacitor element made from the film. On the other hand, in this embodiment, the volume resistivity ρ V23℃ is the volume resistivity ρ at 100°C measured by the above measurement method (1). V100℃ is measured by the above-mentioned measurement method (3). This allows the volume resistivity of the film to be obtained with higher accuracy than the order of magnitude level. In the method for measuring the volume resistivity in this embodiment, one of the reasons for the improved accuracy is that the potential gradient is constant (200 V / μm in this embodiment). Generally, within the range where Ohm's law holds, the volume resistivity will be constant regardless of the voltage at which it is measured (whatever the potential gradient). However, in areas where Ohm's law does not hold (high electric field areas), the volume resistivity will vary depending on the voltage at which it is measured. Specifically, the higher the voltage at which it is measured (the higher the potential gradient), the lower the measured volume resistivity will be. For this reason, it is important to compare the volume resistivity of films under conditions where the potential gradient is the same. In this embodiment, the volume resistivity is calculated with the potential gradient constant, so that, for example, when the volume resistivities of a plurality of types of films are measured, it is possible to determine that the values that would have been evaluated as being almost the same volume resistivity in the conventional method because the values are the same digits are clearly different values. As can be seen from the examples, there is a good correlation between the volume resistivity of the film obtained by the volume resistivity measurement method in this embodiment and the rate of decrease in the insulation resistance value (IR) of the capacitor element in the life test. Note that the relative dielectric constant is a value specific to the molecular structure (conformation and packing) of the resin film. Therefore, the product of the volume resistivity and the relative dielectric constant in this embodiment also has a good correlation with the rate of decrease in the insulation resistance value (IR) in the life test. In addition, in this embodiment, when calculating the volume resistivity from the measured current value, the effective electrode area is not the area of the main electrode, but the area of the space between the main electrode and the guard electrode that is the same distance from the main electrode or closer than the main electrode, which enables more accurate measurement of the current value. From the above, in this embodiment, the higher the volume resistivity, the more suppressed the rate of decrease in the insulation resistance (IR) of the capacitor element in the life test. And the product [ρ V23℃ ×ε r23℃ ], but 1×10 16 If the resistance is Ω·cm or more, it can withstand actual long-term use in an atmosphere of 23°C (room temperature). In addition, the product [ρ V100℃ ×ε r100℃ ], but 1×10 14 If the resistance is Ω·cm or more, it can withstand actual long-term use in an atmosphere of 100°C (high temperature). In addition, the product [ρ V23℃ ×ε r23℃ ], but 1×10 16 If the dielectric constant is Ω·cm or more, it can withstand actual long-term use in an atmosphere of 23°C (normal temperature), and the product [ρ V100℃ ×ε r100℃ ], but 1×10 14The reason why it is said that a resistance of Ω·cm or more means that the material can withstand long-term actual use in an atmosphere at 100°C (high temperature) is that this value is set as the evaluation standard for life tests, and it is assumed that if the value is above this value, there is an extremely high possibility that the material will be able to withstand long-term actual use.
[0077] In this embodiment, the volume resistivity ρ V23℃ Instead, volume resistivity ρ V23℃ and relative dielectric constant ε r23℃ The product of [ρ V23℃ ×ε r23℃ ], 1×10 16 The reason why the resistance is set to Ω·cm or more is as follows. As described above, the higher the volume resistivity of the film in this embodiment, the more suppressed the rate of decrease in the insulation resistance (IR) of the capacitor element in the life test. Therefore, the higher the volume resistivity, the more preferable it is. On the other hand, the larger the relative dielectric constant, the greater the ability to store electricity. In other words, the larger the relative dielectric constant, the greater the capacitance of the capacitor. Therefore, the higher the relative dielectric constant, the more preferable it is. When examining resin materials, there are various materials, such as those having a relatively large volume resistivity but a relatively small relative dielectric constant, and those having a relatively small volume resistivity but a relatively large relative dielectric constant. When considering various such materials, it is expected that those with a relatively large volume resistivity of the film will have a low leakage current of the capacitor element during the life test period, and as a result, the heat generated by the capacitor element will be suppressed, and the deterioration rate will be slower. Therefore, even if the dielectric constant is relatively small, it is believed that the performance will be sufficient for long-term actual use. Conversely, for films with a relatively small volume resistivity, the insulation resistance (IR) of the capacitor element is more likely to decrease than for those with a relatively large volume resistivity, and the rate of deterioration is expected to be somewhat faster. However, when the relative dielectric constant is relatively large, the ability to store electricity is originally high. Therefore, (A) the film area (electrode area) required to obtain the desired capacitance can be reduced, or (B) the film thickness can be increased while maintaining the film area. As a result, the leakage current of the capacitor element during the life test period can be reduced, and heat generation can be suppressed. This point will be explained in more detail. Assume that capacitor elements with the same capacitance are fabricated using films with different dielectric constants. In this case, using a film with a relatively large dielectric constant is advantageous in that it allows a choice from the following three options (1) to (3) to achieve a reduction in leakage current. (1) Reduce the area of the film used while maintaining the same thickness. (2) Make the film thicker without changing the film area. (3) Taking the advantages of the previous two, make the film slightly thicker and the film area slightly smaller. As a result, the decrease in insulation resistance (IR) of the capacitor element is further suppressed, and it is believed that the element will be able to withstand actual long-term use. Therefore, the product of the volume resistivity and the relative dielectric constant is used as an index of whether or not a material can withstand actual long-term use.
[0078] As described above, the dielectric constant is a value specific to the molecular structure (conformation and packing) of a resin film, but it was difficult to accurately measure the dielectric constant of a thin film using conventional methods for measuring the dielectric constant. On the other hand, in this embodiment, the relative dielectric constant ε r23℃ is measured by the above measurement method (2), and the relative dielectric constant ε at 100°C is r100℃is measured by the above-mentioned measurement method (4). This makes it possible to measure the relative dielectric constant of even a thin resin film simply and with good reproducibility. From the above, the product [ρ V23℃ ×ε r23℃ ] and the product [ρ V100℃ ×ε r100℃ ] values, more accurate values can be obtained. As a result, a more accurate value can be obtained as an indicator of whether the material can withstand actual long-term use.
[0079] As described above, the area [ρ V23℃ ×ε r23℃ ] is 1 x 10 16 Ω·cm or more. V23℃ ×ε r23℃ ] is 2 x 10 16 It is preferable that the resistance is 3×10 Ω·cm or more. 16 It is more preferable that the product [ρ V23℃ ×ε r23℃ ] is preferably as large as possible. For example, 1×10 22 Ω cm or less, 1×10 21 It is possible to achieve a resistance of Ω·cm or less.
[0080] As described above, the area [ρ V100℃ ×ε r100℃ ] is 1 x 10 14 Ω·cm or more. V100℃ ×ε r100℃ ] is 2 x 10 14 It is preferable that the resistance is 3×10 Ω·cm or more. 14 More preferably, it should be 1×10 15 More preferably, it is 2×10 15 It is even more preferable that the resistance is 3×10 15 It is particularly preferable that the product [ρ V100℃ ×ε r100℃ ] is preferably as large as possible. For example, 5×10 19 Ω cm or less, 1×1019 It is possible to achieve a resistance of Ω·cm or less.
[0081] The volume resistivity ρ V23℃ is 1 x 10 15 It is preferable that the resistance is 5×10 Ω·cm or more. 15 It is more preferable that the volume resistivity ρ is Ω·cm or more. V23℃ is 1×10 15 When the volume resistivity ρ is Ω·cm or more, the rate of decrease in the insulation resistance value (IR) at 23° C. (room temperature) is further suppressed. V23℃ The larger the value, the better. For example, 5×10 21 Ω cm or less, 5×10 20 It is possible to achieve a resistance of Ω·cm or less.
[0082] Relative permittivity ε r23℃ is preferably 2.0 or more, and more preferably 2.2 or more. r23℃ When the relative dielectric constant ε is 2.0 or more, the capacitance of the capacitor can be increased. r23℃ Although it is preferable that is larger, it can be set to, for example, 9.0 or less, 5.0 or less.
[0083] The volume resistivity ρ V100℃ is 5 x 10 13 It is preferable that the resistance is 5×10 Ω·cm or more. 14 It is more preferable that the volume resistivity ρ is Ω·cm or more. V100℃ 5×10 13 When the volume resistivity ρ is Ω·cm or more, the rate of decrease in the insulation resistance value (IR) at 100° C. (high temperature) is further suppressed. V100℃ The larger the value, the better. For example, 3×10 19 Ω cm or less, 5×10 18 It is possible to achieve a resistance of Ω·cm or less.
[0084] Relative permittivity ε r100℃ is preferably 2.0 or more, and more preferably 2.2 or more. r100℃When the relative dielectric constant ε is 2.0 or more, the capacitance of the capacitor can be increased. r100℃ Although it is preferable that is larger, it can be set to, for example, 9.0 or less, 5.0 or less.
[0085] The resin film is, among others, V23℃ ×ε r23℃ ], but 1×10 16 Ω·cm or more, and the product [ρ V100℃ ×ε r100℃ ], but 1×10 15 Ω·cm or more, and the relative dielectric constant ε r100℃ is preferably 2 or more and 5 or less. V23℃ ×ε r23℃ ], but 1×10 16 Ω·cm or more, and the product [ρ V100℃ ×ε r100℃ ], but 1×10 15 Ω·cm or more, and the relative dielectric constant ε r100℃ When the ratio is 2 or more and 5 or less, the rate of decrease in the insulation resistance (IR) of the capacitor element in a life test is further suppressed.
[0086] The resin film is a log 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃ )] is preferably 5 or less, more preferably 3 or less, and even more preferably 2 or less.
[0087] The log 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃ When the log )] is 5 or less, it can be said that the difference in the rate of decrease in the insulation resistance value (IR) of the capacitor element in the life test is small between 23°C (normal temperature) and 100°C (high temperature). 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃) can be used as an index of heat resistance, and when this index is 5 or less, it can be said that the heat resistance is more excellent. 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃ )] is preferably small, for example, 0.01 or more, 0.1 or more, or 0.5 or more.
[0088] Said [ρ V23℃ ×ε r23℃ )], said [ρ V100℃ ×ε r100℃ ], and the log 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃ )] can be appropriately adjusted by (i) the selection of the type, stereoregularity, ash content, and molecular weight distribution of the resin (raw material resin) constituting the resin film, (ii) the content of the resin relative to the entire resin film, (iii) the longitudinal and transverse stretching ratios and the transverse stretching angle during stretching, (iv) the crystallinity and crystallite size of the resin film, (v) whether or not the resin is subjected to a poling treatment and the applied voltage during the treatment, (vi) the selection of the type and content of additives (especially inorganic fillers), and the like. In this specification, the transverse stretching angle means the following. Transverse stretching angle: When both ends of a first line segment constituting the resin film width at the transverse stretching start point are defined as the first end and the second end, and both ends of a second line segment constituting the resin film width at the transverse stretching end point are defined as the third end and the fourth end, and the first end and the third end are defined as being located on one side of a reference virtual line extending from the midpoint of the first line segment along the flow direction, the angle formed by the first virtual line connecting the first end and the third end and the second virtual line extending from the first end along the flow direction (this angle is less than 90°). The transverse stretching angle is preferably 8.5° or more, more preferably 9.0° or more. The transverse stretching angle is preferably 13.0° or less, more preferably 12.0° or less. When the transverse stretching angle is increased, [ρ V23℃ ×ε r23℃ ] and [ρ V100℃ ×ε r100℃ ] tends to be large.
[0089] The rate of decrease in insulation resistance (IR) in a life test of a capacitor element manufactured using the resin film is preferably 50% or less, more preferably 25% or less, even more preferably 20% or less, even more preferably 15% or less, and particularly preferably 10% or less. The rate of decrease in insulation resistance (IR) is preferably small, but can be, for example, -1000% or more, -500% or more, -100% or more, etc. The rate of decrease in insulation resistance (IR) is a value calculated by the following formula. The method of measuring the insulation resistance of the capacitor element and the method of measuring the insulation resistance after the life test are as follows.
[0090] <Measurement of the insulation resistance value of the capacitor element, measurement of the insulation resistance value after the life test, and calculation of the rate of decrease in the insulation resistance value (IR)> The insulation resistance value of the capacitor element is evaluated using a super insulation resistance meter DSM8104 manufactured by Hioki E.E. Corporation. The rate of decrease in the insulation resistance value is obtained by the following procedure. After leaving the capacitor element at 23°C for 24 hours, a voltage is applied to the capacitor element with a potential gradient of 250V / μm (500V if the film thickness is 2μm or more), and the insulation resistance value is measured 1 minute after the application. This is the insulation resistance value before the life test. Next, the capacitor element is removed from the super insulation resistance meter, and a voltage is applied (loaded) to the capacitor element with a potential gradient of DC 280V / μm from a DC high-voltage power source in a thermostatic chamber at 105°C for 1000 hours. After 1000 hours, the capacitor element is removed and then a discharge resistor is connected to the capacitor element to remove electricity. Next, the capacitor element is left at 23°C for 24 hours, and then the insulation resistance value of the capacitor element is measured. This is the insulation resistance value after the life test. After that, the rate of decrease in the insulation resistance value is calculated. The rate of decrease in the insulation resistance value is evaluated based on the average value of two capacitors. [Insulation resistance decrease rate (%)] = [[(insulation resistance value before life test) - (insulation resistance value after life test)] / ((insulation resistance value before life test)] × 100
[0091] The rate of decrease in (C·IR) during a life test of a capacitor element produced using the resin film is preferably 50% or less, more preferably 30% or less, even more preferably 20% or less, and even more preferably 10% or less. The rate of decrease in (C·IR) (%) is a value calculated by the following formula. If the rate of decrease in (C·IR) (%) is 50% or less, the self-heating of the capacitor element during the life test is kept low, so that the deterioration of the resin film progresses slowly, resulting in a highly reliable capacitor that can withstand long-term use. [(C IR) decrease rate (%)] = [[(capacitor capacity before life test) x (insulation resistance value before life test) - (capacitor capacity after life test) x (insulation resistance value after life test)] / [(capacitor capacity before life test) x (insulation resistance value before life test)]] x 100
[0092] The ash content in the resin constituting the resin film is preferably 35 ppm or less, more preferably 30 ppm or less, and even more preferably 25 ppm or less. The ash content is preferably 5 ppm or more, more preferably 10 ppm or more, even more preferably 15 ppm or more, and even more preferably 20 ppm or more. When a resin film that does not contain additives (see the section on additives described later) is used as the resin film, the ash content refers to a value obtained by the method described in the Examples. On the other hand, when a resin film that contains additives is used as the resin film, the ash content refers to a value obtained by the method described in the Examples using a resin film for ash content measurement made only from raw resin.
[0093] The ash content in the resin (raw resin) constituting the resin film is preferably 5 ppm or more and 35 ppm or less in order to improve the electrical properties as a capacitor while suppressing the generation of low-molecular components having polarity.
[0094] The resin film preferably has a heptane insoluble content of 96% or more and 99.5% or less, more preferably 97.0% or more and 99.3% or less, and even more preferably 97.5% or more and 99.0% or less. The heptane insoluble content is measured by the method described in the Examples.
[0095] The higher the heptane insoluble content, the higher the stereoregularity of the resin. When the heptane insoluble content (HI) of the resin film is 96% or more and 99.5% or less, the moderately high stereoregularity leads to a moderate improvement in the crystallinity of the resin, and the voltage resistance at high temperatures is improved. On the other hand, the solidification (crystallization) speed during cast raw sheet molding becomes moderate, and the film has moderate extensibility.
[0096] The weight average molecular weight Mw of the resin film and the number average molecular weight Mn of the resin film are not particularly limited.
[0097] The molecular weight distribution [(weight average molecular weight Mw) / (number average molecular weight Mn)] of the resin film is preferably 5 or more and 12 or less, more preferably 5.2 or more and 10.5 or less, and even more preferably 5.5 or more and 9 or less.
[0098] When the molecular weight distribution [(weight average molecular weight Mw) / (number average molecular weight Mn)] of the resin film is within the above-mentioned range, it is preferable because it is possible to obtain a suitable resin fluidity during the stretching process, and it is easy to obtain a film with a uniform thickness. It is also preferable from the viewpoint of voltage resistance when used for a capacitor.
[0099] In this specification, the weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) of the resin film are values measured using a gel permeation chromatograph (GPC) device. More specifically, they are values measured using a high-temperature GPC measuring instrument with built-in differential refractometer (RI) HLC-8121GPC-HT (product name) manufactured by Tosoh Corporation. As the GPC column, three TSKgel GMHHR-H(20)HT manufactured by Tosoh Corporation are connected and used. The column temperature is set to 140°C, and trichlorobenzene is passed as an eluent at a flow rate of 1.0 ml / 10 min to obtain measured values of Mw and Mn. A calibration curve for the molecular weight M is created using standard polystyrene manufactured by Tosoh Corporation, and the measured values are converted into polystyrene values to obtain Mw and Mn. Here, the logarithm to the base 10 of the molecular weight M of the standard polystyrene is called the logarithmic molecular weight ("Log(M)").
[0100] The resin film has a crystallite size of preferably 9 nm to 15 nm, more preferably 10 nm to 13.5 nm, even more preferably 11 nm to 12.2 nm, and particularly preferably 11.3 nm to 12.0 nm, calculated from the half-width of the reflection peak of the α-crystal (040) plane measured by wide-angle X-ray diffraction using Scherrer's formula. The crystallite size is measured by the method described in the Examples.
[0101] When the crystallite size of the resin film is 15 nm or less, the leakage current is small and the voltage resistance at room temperature and high temperature is preferably improved, whereas when the crystallite size is 9 nm or more, it is preferable from the viewpoint of maintaining the mechanical strength and melting point of the resin film (particularly, polypropylene film).
[0102] The resin film has a plane orientation coefficient of preferably 0.010 to 0.016, more preferably 0.011 to 0.0155, even more preferably 0.0115 to 0.015, still more preferably 0.0121 to 0.0134, and particularly preferably 0.0125 to 0.0131.
[0103] It is preferable that the plane orientation coefficient of the resin film is within the above range, since this can further reduce dielectric breakdown under high temperature and high voltage conditions.
[0104] <Plane orientation coefficient ΔP> In this specification, the "plane orientation coefficient ΔP" refers to the plane orientation coefficient ΔP (where ΔP = (ΔNyz + ΔNxz) / 2) calculated from the birefringence values ΔNyz and ΔNxz in the thickness direction of the resin film obtained by optical birefringence measurement. In the specification, the "birefringence value ΔNyz" in the thickness direction of the resin film refers to the birefringence value ΔNyz in the thickness direction obtained by optical birefringence measurement. More specifically, if the main axes in the in-plane direction of the film are the x-axis and y-axis, the thickness direction of the film (the normal direction to the in-plane direction) is the z-axis, and the slow axis in the in-plane direction with the higher refractive index is the x-axis, the birefringence value ΔNyz is the value obtained by subtracting the three-dimensional refractive index in the z-axis direction from the three-dimensional refractive index in the y-axis direction.
[0105] In addition, in this specification, the "birefringence value ΔNxz" in the thickness direction of the resin film refers to the birefringence value ΔNxz in the thickness direction determined by optical birefringence measurement, and more specifically, the birefringence value ΔNxz is the value obtained by subtracting the three-dimensional refractive index in the z-axis direction from the three-dimensional refractive index in the x-axis (slow axis) direction.
[0106] The birefringence values ΔNyz and / or ΔNxz can be used as an index of the strength of the orientation of the film. When the orientation strength of the film is strong, the three-dimensional refractive index in the y-axis direction and / or the three-dimensional refractive index in the x-axis direction, which are the in-plane refractive indexes, becomes high, and the three-dimensional refractive index in the z-axis direction, which is the refractive index in the thickness direction, becomes low, so that the birefringence values ΔNyz and / or ΔNxz become large.
[0107] In this embodiment, in order to measure the "birefringence value ΔNyz" in the thickness direction of the resin film, specifically, a retardation measuring device RE-100 manufactured by Otsuka Electronics Co., Ltd. is used. The retardation (retardation) is measured using a tilt method. More specifically, the main axes in the in-plane direction of the film are the x-axis and y-axis, and the thickness direction of the film (normal direction to the in-plane direction) is the z-axis, and the slow axis in the in-plane direction with a higher refractive index is the x-axis. The x-axis is the tilt axis, and each retardation value is obtained when tilted 10° at a time with respect to the z-axis in the range of 0° to 50°. From the obtained retardation value, the birefringence ΔNyz in the y-axis direction with respect to the thickness direction (z-axis direction) is calculated using the method described in the non-patent document "Awaya Yutaka, Introduction to Polarizing Microscopes of Polymer Materials, pp. 105-120, 2001". First, for each tilt angle φ, the measured retardation value R is divided by the thickness d corrected for tilt to obtain R / d. For each R / d at φ=10°, 20°, 30°, 40°, and 50°, the difference between R / d at φ=0° is calculated, and further divided by sin2r (r: refraction angle) to obtain the birefringence ΔNzy at each φ, and the positive and negative signs are reversed to obtain the birefringence value ΔNyz. The birefringence value ΔNyz is calculated as the average value of ΔNyz at φ=20°, 30°, 40°, and 50°. For example, in the sequential stretching method, when the stretching ratio in the TD direction (width direction) is higher than the stretching ratio in the MD direction (flow direction), the TD direction becomes the slow axis (x axis) and the MD direction becomes the y axis. In addition, when polypropylene is used, the value of the refraction angle r at each inclination angle for polypropylene is described on page 109 of the above-mentioned document.
[0108] In addition, in this embodiment, the "birefringence value ΔNxz" in the thickness direction of the resin film is calculated by dividing the retardation value R measured at an inclination angle φ=0° by the thickness d and then dividing the ΔNzy obtained above to calculate the birefringence value ΔNxz.
[0109] When the resin film is oriented in the plane direction (x-axis direction and / or y-axis direction), the refractive index Nz in the thickness direction changes, the birefringence value ΔNyz and / or ΔNxz increases, and the voltage resistance improves (the dielectric breakdown voltage increases). This is believed to be due to the following reasons. When the molecular chains of the resin (e.g., polypropylene) are oriented in the plane direction, the refractive index Nz in the thickness direction decreases. The electrical conductivity in the film thickness direction is transmitted between molecular chains, so it is low. Therefore, when the resin molecular chains (e.g., polypropylene molecular chains) are oriented in the plane direction (birefringence value ΔNyz and / or ΔNxz is large), the electrical conductivity in the film thickness direction can be transmitted between molecular chains, so it is believed that the voltage resistance improves compared to when the resin molecular chains are not oriented in the plane direction (birefringence value ΔNyz and / or ΔNxz is small).
[0110] In general, the orientation of the molecular chains of the resin can be changed by changing the film-forming conditions (such as adjusting the stretching ratio), thereby controlling the "birefringence value ΔNyz" and / or the "birefringence value ΔNxz". In addition, the "birefringence value ΔNyz" and / or the "birefringence value ΔNxz" can also be controlled by changing the properties of the resin (such as molecular weight, degree of polymerization, and molecular weight distribution).
[0111] The "plane orientation coefficient ΔP" is calculated by substituting the birefringence values ΔNyz and ΔNxz into the formula: ΔP = (ΔNyz + ΔNxz) / 2. In the present invention, one feature is that the "plane orientation coefficient ΔP" is calculated by taking into account not only the orientation strength in the y-axis direction represented by the birefringence value ΔNyz, but also the orientation strength in the x-axis direction represented by the birefringence value ΔNxz. The plane orientation coefficient ΔP is a relatively small value, for example, even if the birefringence value ΔNyz is very large, if the birefringence value ΔNxz is extremely small. Assuming that the difference in length between the long axis and the short axis of the cross section of a branched chain of the resin is large, one of the birefringence values may be extremely small, so that the long axis direction approaches (or coincides with) the film thickness direction, in which case it is considered that the electrical conductivity in the film thickness direction increases and the voltage resistance decreases. Therefore, it is considered that the birefringence value ΔNyz and the birefringence value ΔNxz are not both extremely low values, and therefore the plane orientation coefficient ΔP is equal to or greater than a certain value, thereby improving the voltage resistance. The specific method for measuring the plane orientation coefficient is the method described in the Examples.
[0112] The resin film has a melting point of preferably 170°C or more and 176°C or less, more preferably 171°C or more and 175.5°C or less, even more preferably 171.5°C or more and 175°C or less, and particularly preferably 172°C or more and 174.5°C or less.
[0113] When the melting point of the resin film is 170° C. or higher, the voltage resistance and thermal dimensional stability at high temperatures are excellent. On the other hand, when the melting point is 176° C. or lower, the rigidity of the film becomes appropriate, and it is easy to form it into a stretched film. The melting point is measured by the method described in the Examples.
[0114] The resin film preferably has a melting enthalpy of 90 J / g or more and 125 J / g or less, more preferably 100 J / g or more and 123 J / g or less, and even more preferably 108 J / g or more and 122 J / g or less.
[0115] The melting enthalpy of the resin film is preferably 90 J / g or more since the crystallites are strong. On the other hand, the melting enthalpy of the resin film is preferably 125 J / g or less since the crystallite size is appropriately small. The melting enthalpy is measured by the method described in the Examples.
[0116] The resin film has a thickness preferably in the range of 0.8 to 22 μm, more preferably in the range of 1.2 to 12.0 μm, even more preferably in the range of 1.4 to 6.0 μm, still more preferably in the range of 1.5 to 4.0 μm, even more preferably in the range of 1.5 to 3.0 μm, and particularly preferably in the range of 1.5 to 2.9 μm.
[0117] When the thickness is 22 μm or less, the capacitance can be increased, making it suitable for use in a capacitor. From the viewpoint of manufacturing, the thickness can be set to 0.8 μm or more.
[0118] The thickness of the resin film is preferably in the range of 0.8 to 6 μm. When the capacitor element generates heat, the temperature of the resin film also rises inside the capacitor element, causing a decrease in the insulation resistance value (IR). Therefore, if the thickness of the resin film is reduced, the capacitor element can be made smaller for the same capacitance, and the specific surface area of the capacitor element increases, which is advantageous for heat dissipation. Therefore, if the thickness is 6 μm or less, the decrease in capacitance can be further suppressed. In addition, since the decrease in capacitance can be further suppressed, the decrease rate (%) of (C·IR) can also be further suppressed. In addition, when the thickness of the resin film is 6 μm or less, the capacitance per unit volume can be increased when the film is made into a capacitor element, so that the film can be suitably used for a capacitor. In addition, from the viewpoint of film formation stability, the thickness of the resin film is preferably 0.8 μm or more. This point will be explained in detail below. The thinner the resin film, the greater the capacitance per unit volume. More specifically, the capacitance C is expressed as follows using the dielectric constant ε, the electrode area S, and the dielectric thickness d (thickness d of the resin film): C=εS / d Here, in the case of a film capacitor, the thickness of the electrodes is three or more orders of magnitude thinner than the thickness of the resin film (dielectric), so if the volume of the electrodes is ignored, the volume V of the capacitor can be expressed as follows: V=Sd Therefore, from the above two equations, the capacitance per unit volume, C / V, is expressed as follows: C / V=ε / d 2 As can be seen from the above formula, the capacitance per unit volume (C / V) is inversely proportional to the square of the resin film thickness. Also, the dielectric constant ε is determined by the material used. Therefore, unless the material is changed, it is not possible to improve the capacitance per unit volume (C / V) other than by reducing the thickness. The electrode area does not affect the capacitance per unit volume (C / V). This point will be explained below. Consider the case where a capacitor is made by winding a film of the same material and the same thickness. For example, suppose the number of turns is increased and the film is wound 10 times longer (the electrode area is 10 times larger). This increases the capacitance by 10 times, but the volume also increases by 10 times, so the capacitance per unit volume (C / V) does not change even if the electrode area changes. The above explanation is idealized for ease of understanding. In reality, for example, there may be a small gap between the films, or there may be a fringe effect at the electrode ends, so the capacitance per unit volume (C / V) may vary slightly depending on the area. However, it can be understood that the capacitance per unit volume (C / V) is generally determined by the thickness of the resin film. In view of the above, it is preferable that the thickness of the resin film is as thin as possible within a range that ensures film formation stability, and therefore the thickness of the resin film is preferably 6 μm or less.
[0119] The thickness of the resin film is a value measured in accordance with JIS-C2330, except that the thickness was measured at 100±10 kPa using a paper thickness measuring instrument MEI-11 manufactured by Citizen Seimitsu Co., Ltd.
[0120] The resin film may be a biaxially stretched film, a uniaxially stretched film, or a non-stretched film. Among them, a biaxially stretched film is preferable from the viewpoint of increasing the plane orientation coefficient.
[0121] As described above, the resin film contains a crystalline thermoplastic resin as a main component. In this specification, "containing a crystalline thermoplastic resin as a main component" means that the resin film contains 50% by mass or more of the crystalline thermoplastic resin with respect to the entire resin film (when the entire resin film is taken as 100% by mass). The content of the crystalline thermoplastic resin with respect to the entire resin film is preferably 75% by mass or more, and more preferably 90% by mass or more. The upper limit of the content of the crystalline thermoplastic resin with respect to the entire resin film is, for example, 100% by mass, 98% by mass, etc.
[0122] The crystalline thermoplastic resin is preferably a resin that satisfies at least one of the following: (a) the main chain is an aliphatic hydrocarbon; (b) the main chain has an amide bond; and (c) the main chain has an ether bond. (a) Examples of crystalline thermoplastic resins whose main chain is an aliphatic hydrocarbon include polypropylene resin, polyethylene resin, polyvinylidene fluoride (PVDF) resin, and the like. In this specification, the term "aliphatic hydrocarbons" refers to both saturated and unsaturated hydrocarbons. (b) Examples of crystalline thermoplastic resins having an amide bond in the main chain include nylon 6 (PA6) and nylon 66 (PA66). (c) Examples of crystalline thermoplastic resins having an ether bond in the main chain include polyether ether ketone (PEEK) resin and polyacetal (POM) resin. The crystalline thermoplastic resin may be a copolymer that satisfies two or more of the above (a) to (c).
[0123] The crystalline thermoplastic resin may be a resin in which at least one hydrogen atom is bonded to each of the carbon atoms constituting the main chain of the crystalline thermoplastic resin. Examples of crystalline thermoplastic resins in which at least one hydrogen atom is bonded to each of the carbon atoms that make up the main chain include polypropylene resin, polyethylene resin, polyphenylene sulfide (PPS) resin, polyether ether ketone (PEEK) resin, and polyacetal (POM) resin. In this specification, "at least one hydrogen atom is bonded to each of the carbon atoms constituting the main chain" means that when the main chain contains a benzene ring, at least one hydrogen atom is bonded to the benzene ring, and when the main chain contains atoms other than carbon atoms, the atoms other than carbon atoms may or may not be bonded to hydrogen atoms.
[0124] The crystalline thermoplastic resin may be used alone or in combination of two or more kinds. It is particularly preferable to use two or more kinds of the crystalline thermoplastic resin in combination.
[0125] Among them, the crystalline thermoplastic resin is preferably a polypropylene resin, which has a relatively high volume resistivity, and therefore, when the crystalline thermoplastic resin is a polypropylene resin, the rate of decrease in the insulation resistance (IR) of the capacitor element during a life test can be suitably suppressed.
[0126] The weight average molecular weight Mw of the polypropylene resin is preferably 250,000 or more and 450,000 or less, more preferably 250,000 or more and 400,000 or less. When the weight average molecular weight Mw of the polypropylene resin is 250,000 or more and 450,000 or less, the resin fluidity is moderate. As a result, it is easy to control the thickness of the cast raw sheet, and it is easy to prepare a thin stretched film. In addition, it is possible to impart moderate stretchability to the cast raw sheet. When two or more polypropylene resins are used, it is preferable to use a polypropylene resin having an Mw of 250,000 or more and less than 330,000 and a polypropylene resin having an Mw of 330,000 or more and 450,000 or less in combination.
[0127] The molecular weight distribution of the polypropylene resin [(weight average molecular weight Mw) / (number average molecular weight Mn)] is preferably 5 or more and 12 or less, more preferably 5 or more and 11 or less, and even more preferably 5 or more and 10 or less. When two or more polypropylene resins are used, it is preferable to use a polypropylene resin having the above-mentioned molecular weight distribution of 5 or more and less than 8.5 in combination with a polypropylene resin having the above-mentioned molecular weight distribution of 8.5 or more and 11 or less.
[0128] In this specification, the weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) of the polypropylene resin are values measured using a gel permeation chromatograph (GPC) device. More specifically, they are values measured using a high-temperature GPC measuring device with built-in differential refractometer (RI) manufactured by Tosoh Corporation, HLC-8121GPC-HT (product name). As the GPC column, three TSKgel GMHHR-H(20)HT columns manufactured by Tosoh Corporation are connected and used. The column temperature is set to 140°C, and trichlorobenzene is passed as an eluent at a flow rate of 1.0 ml / 10 min to obtain measured values of Mw and Mn. A calibration curve for the molecular weight M is created using standard polystyrene manufactured by Tosoh Corporation, and the measured values are converted into polystyrene values to obtain Mw and Mn. Here, the logarithm to the base 10 of the molecular weight M of the standard polystyrene is called the logarithmic molecular weight ("Log(M)").
[0129] Differential distribution value difference D of polypropylene resin M is preferably -5% or more and 14% or less, more preferably -4% or more and 12% or less, and further preferably -4% or more and 10% or less. M " is the difference obtained by subtracting the differential distribution value when the logarithmic molecular weight Log(M) is 6.0 from the differential distribution value when the logarithmic molecular weight Log(M) is 4.5 in a molecular weight differential distribution curve. In addition, "Differential distribution value difference D M is -5% or more and 14% or less" means that, when comparing the logarithmic molecular weight Log(M)=4.5, which is a representative distribution value of components with a molecular weight of 10,000 to 100,000 on the low molecular weight side (hereinafter also referred to as "low molecular weight components"), with the logarithmic molecular weight Log(M)=6.0, which is a representative distribution value of components with a molecular weight of around 1 million on the high molecular weight side (hereinafter also referred to as "high molecular weight components"), if the difference is positive, it can be understood that there are more low molecular weight components, and if the difference is negative, there are more high molecular weight components.
[0130] In other words, even if the molecular weight distribution Mw / Mn is 5 to 12, this merely indicates the width of the molecular weight distribution, and does not reveal the quantitative relationship between the high molecular weight components and the low molecular weight components therein. Therefore, from the viewpoint of stable film-forming property and thickness uniformity of the cast raw sheet, it is preferable to use a polypropylene resin that has a wide molecular weight distribution and at the same time contains an appropriate amount of low molecular weight components, so that the differential distribution value difference between the components with molecular weights of 10,000 to 100,000 is -5% or more and 14% or less compared to the component with a molecular weight of 1 million.
[0131] The differential distribution value is a value obtained using GPC as follows. A curve showing intensity versus time (generally called an "elution curve") obtained by a GPC differential refractive index (RI) detector is used. A calibration curve obtained using standard polystyrene is used to convert the time axis into logarithmic molecular weight (Log(M)), thereby converting the elution curve into a curve showing intensity versus Log(M). Since the RI detection intensity is proportional to the component concentration, if the total area of the curve showing intensity is taken as 100%, an integral distribution curve for the logarithmic molecular weight Log(M) can be obtained. The differential distribution curve is obtained by differentiating this integral distribution curve with Log(M). Therefore, "differential distribution" means the differential distribution of the concentration fraction versus the molecular weight. From this curve, the differential distribution value at a specific Log(M) is read.
[0132] The heptane insoluble content (HI) of the polypropylene resin is preferably 96.0% or more, more preferably 97.0% or more. The heptane insoluble content (HI) of the polypropylene resin is preferably 99.5% or less, more preferably 99.0% or less. Here, the higher the heptane insoluble content, the higher the stereoregularity of the resin. When the heptane insoluble content (HI) is 96.0% or more and 99.5% or less, the moderately high stereoregularity leads to a moderate improvement in the crystallinity of the resin, and the voltage resistance at high temperatures is improved. On the other hand, the rate of solidification (crystallization) during cast raw sheet molding becomes moderate, and the resin has moderate extensibility. The heptane insoluble content (HI) is measured by the method described in the Examples.
[0133] The melt flow rate (MFR) of the polypropylene resin is preferably 1.0 to 8.0 g / 10 min, more preferably 1.5 to 7.0 g / 10 min, and further preferably 2.0 to 6.0 g / 10 min. The melt flow rate of the polypropylene resin is measured by the method described in the Examples.
[0134] The polypropylene resin can be produced by a generally known polymerization method, for example, a gas phase polymerization method, a bulk polymerization method, and a slurry polymerization method.
[0135] The polymerization may be a single-stage polymerization using one polymerization reactor, or a multi-stage polymerization using two or more polymerization reactors. The polymerization may be carried out by adding hydrogen or a comonomer as a molecular weight modifier to the reactor.
[0136] The catalyst used in the polymerization can be a generally known Ziegler-Natta catalyst, and is not particularly limited as long as the polypropylene resin can be obtained. The catalyst may contain a cocatalyst component or a donor. By adjusting the catalyst and polymerization conditions, the molecular weight, molecular weight distribution, stereoregularity, etc. can be controlled.
[0137] The molecular weight distribution of the polypropylene resin can be adjusted by resin mixing (blending). For example, a method of mixing two or more resins having different molecular weights or molecular weight distributions can be mentioned. In general, a two-type polypropylene mixture in which the main resin is 55% by mass or more and 90% by mass or less, assuming that the total resin is 100% by mass, and a resin having a higher or lower average molecular weight than the main resin is mixed is preferable because it is easy to adjust the amount of low molecular weight components.
[0138] When the above-mentioned mixing and adjusting method is adopted, the melt flow rate (MFR) may be used as a guide for the average molecular weight. In this case, it is preferable that the difference in MFR between the main resin and the additive resin is about 1 to 30 g / 10 min from the viewpoint of convenience during adjustment.
[0139] The method for mixing the resins is not particularly limited, and examples thereof include a method in which polymer powders or pellets of the main resin and the additive resin are dry-blended using a mixer or the like, and a method in which polymer powders or pellets of the main resin and the additive resin are fed to a kneader and melt-kneaded to obtain a blended resin.
[0140] The mixer and the kneader are not particularly limited. The kneader may be of a single screw type, a twin screw type, or a multi-screw type having more than one screw. In the case of a twin or more screw type, the kneader may be of either a co-rotating or counter-rotating type.
[0141] In the case of blending by melt kneading, the kneading temperature is not particularly limited as long as a good kneaded product is obtained. In general, it is in the range of 200°C to 300°C, and from the viewpoint of suppressing deterioration of the resin, 230°C to 270°C is preferable. In addition, in order to suppress deterioration during kneading and mixing of the resin, an inert gas such as nitrogen may be purged into the kneader. The melt kneaded resin may be pelletized to an appropriate size using a generally known granulator. In this way, mixed polypropylene raw material resin pellets can be obtained.
[0142] The total ash content resulting from polymerization catalyst residues and the like contained in the polypropylene raw material resin is preferably 50 ppm or less based on the polypropylene resin (100 parts by weight).
[0143] The total ash content (total ash content contained in the polypropylene raw material resin) is preferably 5 ppm or more and 35 ppm or less, more preferably 5 ppm or more and 30 ppm or less, and even more preferably 10 ppm or more and 25 ppm or less, in order to improve the electrical characteristics as a capacitor while suppressing the generation of polar low molecular weight components.
[0144] Hereinafter, when two or more kinds of polypropylene resins are used, each polypropylene resin will be described.
[0145] When two or more polypropylene resins are used, the following combinations of polypropylene resin A-1 and polypropylene resin B-1, polypropylene resin A-2 and polypropylene resin B-2, or polypropylene resin A-3 and polypropylene resin B-3 are preferred. In this embodiment, the term "polypropylene resin A" includes the concepts of polypropylene resin A-1, polypropylene resin A-2, and polypropylene resin A-3. The term "polypropylene resin B" includes the concepts of polypropylene resin B-1, polypropylene resin B-2, and polypropylene resin B-3. It is preferable that the polypropylene resins A, A-1, A-2, and A-3, and the polypropylene resins B, B-1, B-2, and B-3 are all linear polypropylene resins. <Polypropylene resin A> (Polypropylene resin A-1) Differential distribution value difference D M A polypropylene resin having a molecular weight of 8.0% or more. (Polypropylene resin A-2) Polypropylene resin with a heptane insoluble (HI) content of 98.5% or less. (Polypropylene resin A-3) Polypropylene resin with a melt flow rate (MFR) at 230°C of 4.0 to 10.0 g / 10 min. <Polypropylene resin B> (Polypropylene resin B-1) Differential distribution value difference D M A polypropylene resin having less than 8.0%. (Polypropylene resin B-2) Polypropylene resin with heptane insoluble (HI) content exceeding 98.5%. (Polypropylene resin B-3) Polypropylene resin with a melt flow rate (MFR) at 230°C of 0.1 to 3.9 g / 10 min.
[0146] The weight average molecular weight Mw of the polypropylene resin A is preferably 250,000 to 450,000, more preferably 250,000 to 400,000, and even more preferably 250,000 to 340,000. When the weight average molecular weight Mw of the polypropylene resin A is 250,000 to 450,000, the resin fluidity is moderate. As a result, it is easy to control the thickness of the cast raw sheet, and it is easy to prepare a thin biaxially stretched polypropylene film. In addition, it is preferable because the thickness of the cast raw sheet and the biaxially stretched polypropylene film is less likely to be uneven, and moderate stretchability is obtained.
[0147] The molecular weight distribution Mw / Mn of the polypropylene resin A is preferably 8.5 or more and 12.0 or less, more preferably 8.5 or more and 11.0 or less, and even more preferably 9.0 or more and 11.0 or less.
[0148] When the molecular weight distribution Mw / Mn of the polypropylene resin A is within the above preferred range, the cast raw sheet and the biaxially oriented polypropylene film are less likely to have uneven thickness and can preferably have suitable stretchability.
[0149] Differential distribution value difference D of polypropylene resin A M is preferably 8.0% or more, more preferably 8.0% or more and 18.0% or less, even more preferably 8.5% or more and 17.0% or less, and particularly preferably 9.0% or more and 16.0% or less.
[0150] Differential distribution value difference D M When the ratio is 8.0% or more and 18.0% or less, the low molecular weight component is contained in a proportion of 8.0% or more and 18.0% or less as compared with the high molecular weight component. Therefore, the frequency of breakage in the stretching process can be reduced, and continuous film formability is improved, which is preferable.
[0151] The heptane insoluble matter (HI) of the polypropylene resin A is preferably 96.0% or more, more preferably 97.0% or more. The heptane insoluble matter (HI) of the polypropylene resin A is preferably 99.5% or less, more preferably 98.5% or less, and even more preferably 98.0% or less.
[0152] The melt flow rate (MFR) of polypropylene resin A at 230°C is preferably 1.0 to 15.0 g / 10 min, more preferably 2.0 to 10.0 g / 10 min, further preferably 4.0 to 10.0 g / 10 min, and particularly preferably 4.3 to 6.0 g / 10 min. When the MFR of polypropylene resin A at 230°C is within the above range, the flow characteristics in the molten state are excellent, so that unstable flow such as melt fracture is unlikely to occur, and breakage during stretching is also suppressed. Therefore, there is an advantage that the formation of thin-walled parts that are prone to dielectric breakdown is suppressed because the film thickness uniformity is good.
[0153] The content of polypropylene resin A is preferably 55% by mass or more and 90% by mass or less, more preferably 60% by mass or more and 85% by mass or less, and even more preferably 60% by mass or more and 80% by mass or less, based on the entire biaxially oriented polypropylene film.
[0154] The weight average molecular weight Mw of the polypropylene resin B is preferably 300,000 or more and 400,000 or less, more preferably 330,000 or more and 380,000 or less, and even more preferably 350,000 or more and 380,000 or less.
[0155] The molecular weight distribution Mw / Mn of the polypropylene resin B is preferably 6.0 or more and less than 8.5, more preferably 6.5 or more and 8.4 or less, and even more preferably 7.0 or more and 8.3 or less.
[0156] When the molecular weight distribution Mw / Mn of the polypropylene resin B is within the above preferred range, the cast raw sheet and the biaxially oriented polypropylene film are less likely to have uneven thickness and can have appropriate stretchability, which is preferable.
[0157] Differential distribution value difference D of polypropylene resin B M is preferably less than 8.0%, more preferably −20.0% or more and less than 8.0%, further preferably −10.0% or more and 7.9% or less, and particularly preferably −5.0% or more and 7.5% or less.
[0158] The heptane insoluble matter (HI) of polypropylene resin B is preferably 97.5% or more, more preferably 98% or more, even more preferably more than 98.5%, and particularly preferably 98.6% or more. The heptane insoluble matter (HI) of polypropylene resin B is preferably 99.5% or less, more preferably 99% or less.
[0159] The melt flow rate (MFR) of polypropylene resin B at 230° C. is preferably from 0.1 to 6.0 g / 10 min, more preferably from 0.1 to 5.0 g / 10 min, and further preferably from 0.1 to 3.9 g / 10 min.
[0160] When polypropylene resin B is used as the polypropylene resin, the content of polypropylene resin B is preferably 10% by mass or more and 45% by mass or less, more preferably 15% by mass or more and 40% by mass or less, and even more preferably 20% by mass or more and 40% by mass or less, assuming that the polypropylene resin is 100% by mass.
[0161] When polypropylene resin A and polypropylene resin B are used in combination as the polypropylene resin, the polypropylene resin preferably contains 55 to 90 weight % of polypropylene resin A and 45 to 10 weight % of polypropylene resin B, more preferably 60 to 85 weight % of polypropylene resin A and 40 to 15 weight % of polypropylene resin B, and particularly preferably 60 to 80 weight % of polypropylene resin A and 40 to 20 weight % of polypropylene resin B, assuming the entire polypropylene resin to be 100 mass %.
[0162] When the polypropylene resin contains polypropylene resin A and polypropylene resin B, the biaxially stretched polypropylene film is in a finely mixed state (phase-separated state) of polypropylene resin A and polypropylene resin B, thereby improving the voltage resistance at high temperatures.
[0163] Above, each polypropylene resin in the case where two or more kinds of polypropylene resins are used has been explained.
[0164] The resin film has a product [ρ V23℃ ×ε r23℃ ], but 1×10 16 Ω·cm or more, and the product [ρ V100℃ ×ε r100℃ ], but 1×10 14 The crystalline thermoplastic resin may contain a resin other than the crystalline thermoplastic resin as long as the resistance is within the range of Ω·cm or more. The other resins include non-crystalline thermoplastic resins. Examples of the non-crystalline thermoplastic resin include polyamideimide (PAI) and polycarbonate (PC).
[0165] The resin film may contain an additive. By containing an additive in the resin film, the product [ρ V23℃ ×ε r23℃ ], the product [ρ V100℃ ×ε r100℃ ], the log 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×εr100℃ )] value can be adjusted.
[0166] Examples of the additives include antioxidants, chlorine absorbers, ultraviolet absorbers, lubricants, plasticizers, flame retardants, antistatic agents, inorganic fillers, organic fillers, etc. Examples of the inorganic fillers include barium titanate, strontium titanate, aluminum oxide, etc. It is preferable that the resin film does not contain a crystal nucleating agent (particularly, an α crystal nucleating agent). As crystal nucleating agents, there are those that are soluble in resin (dissolved nucleating agents) and those that are insoluble in resin (dispersed nucleating agents). Examples of dissolved nucleating agents include nonitol-based nucleating agents and sorbitol-based nucleating agents, but the molecular weight of dissolved nucleating agents is very small compared to thermoplastic resins. Therefore, dissolved nucleating agents added to thermoplastic resins tend to bleed out onto the film surface during the manufacturing process of the resin film, gradually contaminating the surface of the manufacturing equipment (particularly the metal roll that contacts the film). If the contamination accumulates, it becomes necessary to stop the manufacturing equipment and remove the contamination, which may lead to a deterioration in productivity. On the other hand, examples of dispersed nucleating agents include talc, mica, phosphate metal salt-based nucleating agents, and carboxylate metal salt-based nucleating agents, but the interface between the thermoplastic resin and the dispersed nucleating agent tends to become a conductive path, which may reduce the voltage resistance. Furthermore, if the amount of ionic substances contained in the film increases because the crystal nucleating agent, the thermal decomposition product of the crystal nucleating agent, or the impurities contained in the crystal nucleating agent are ionic substances, the ionic electrical conduction increases, causing the volume resistivity to deteriorate. For these reasons, it is preferable that the resin film does not contain a crystal nucleating agent (especially an α crystal nucleating agent).
[0167] When the resin film is a biaxially stretched resin film, a cast raw sheet before stretching for producing the biaxially stretched resin film can be prepared as follows.
[0168] First, crystalline thermoplastic resin pellets, dry-mixed crystalline thermoplastic resin pellets, or mixed crystalline thermoplastic resin pellets previously prepared by melt-kneading are fed into an extruder and heated to melt. The extruder rotation speed during heating and melting is preferably from 5 to 40 rpm, and more preferably from 10 to 30 rpm. The melt-kneading temperature varies depending on the type of thermoplastic resin, but in the case of polypropylene resin, the extruder temperature during heating and melting is preferably 220 to 280° C., more preferably 230 to 270° C. The resin temperature during heating and melting is preferably 220 to 280° C., more preferably 230 to 270° C. The resin temperature during heating and melting is a value measured by a thermometer inserted in the extruder. The extruder rotation speed, extruder temperature setting, and resin temperature during heat melting are selected taking into consideration the physical properties of the crystalline thermoplastic resin used. By setting the resin temperature during heat melting within the above-mentioned range, deterioration of the resin can be suppressed.
[0169] Next, the molten resin is extruded into a sheet using a T-die, and then cooled and solidified on at least one metal drum to form an unstretched cast raw sheet. The surface temperature of the metal drum (the temperature of the metal drum that first comes into contact after extrusion) is preferably 50 to 100° C., and more preferably 60 to 80° C. The surface temperature of the metal drum can be determined depending on the physical properties of the crystalline thermoplastic resin used, etc.
[0170] In the case of polypropylene resin, the melt flow rate (MFR) of the cast raw sheet is preferably 1.0 to 9.0 g / 10 min, more preferably 2.0 to 8.0 g / 10 min, and further preferably 3.0 to 7.0 g / 10 min. The melt flow rate of the polypropylene film is measured by the method described in the Examples. The thickness of the cast raw sheet is not particularly limited as long as the resin film can be obtained, but is usually preferably 0.05 mm to 2 mm, and more preferably 0.1 mm to 1 mm.
[0171] The resin film can be produced by subjecting the resin cast raw sheet to a stretching treatment. The stretching is preferably biaxial stretching in which the sheet is oriented biaxially in the machine direction and the transverse direction, and the stretching method is preferably a sequential biaxial stretching method. In the sequential biaxial stretching method, for example, the cast raw sheet is first kept at a temperature of 100 to 170°C and passed between rolls having a speed difference to stretch the sheet 3 to 7 times in the machine direction. The sheet is then introduced into a tenter and stretched 3 to 11 times in the transverse direction. After that, the sheet is relaxed 2 to 10 times and heat-set. As a result of the above, a biaxially stretched resin film is obtained.
[0172] The resin film may be subjected to corona discharge treatment online or offline after the stretching and heat fixing processes in a post-process such as a metal deposition process, in order to enhance the adhesive properties. The corona discharge treatment can be performed using a known method. It is preferable to perform the treatment using air, carbon dioxide gas, nitrogen gas, or a mixture of these gases as the atmospheric gas.
[0173] In order to process the resin film into a capacitor, a metal layer may be laminated on one or both sides of the resin film to form a metal layer-integrated resin film. The metal layer functions as an electrode. The metal used for the metal layer may be, for example, a single metal such as zinc, lead, silver, chromium, aluminum, copper, or nickel, a mixture of a plurality of metals, or an alloy of a plurality of metals. In consideration of the environment, economy, and capacitor performance, zinc and aluminum are preferred.
[0174] Examples of the method for laminating a metal layer on one or both sides of the resin film include vacuum deposition and sputtering. From the viewpoints of productivity and economy, vacuum deposition is preferred. Examples of the vacuum deposition method include the crucible method and the wire method, but are not particularly limited and the most suitable method can be selected as appropriate.
[0175] The margin pattern when laminating the metal layer by vapor deposition is not particularly limited, but in order to improve the characteristics of the capacitor such as safety, it is preferable to apply a pattern including a so-called special margin, such as a fishnet pattern or a T-margin pattern, on one side of the film. This is effective in terms of increasing safety and preventing the capacitor from being destroyed or short-circuited.
[0176] As a method for forming the margin, a generally known method such as a tape method or an oil method can be used without any limitation.
[0177] The metal layer-integrated resin film can be laminated or wound by a conventionally known method to form a film capacitor. EXAMPLES
[0178] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.
[0179] [Crystalline thermoplastic resin] The crystalline thermoplastic resins used to produce the resin films of the Examples and Comparative Examples are shown in Table 1. The types of resins are shown in Table 1. In Table 1, PP indicates linear polypropylene resin. Resin A in Table 1 is a product manufactured by Prime Polymer Co., Ltd. Resin B is HPT-1 manufactured by Daehan Petrochemicals Co., Ltd. Resin C is HC300BF manufactured by Borealis Corporation Resin D is HF500N manufactured by Basell Corporation Resin E is HP400R manufactured by Basell Corporation Resin F is HP501L manufactured by Basell Corporation. Table 1 shows the number average molecular weight (Mn), weight average molecular weight (Mw), and molecular weight distribution (Mw / Mn) of Resins A to F. These values are values in the form of raw material resin pellets. The measurement method is as follows.
[0180] <Number average molecular weight (Mn), weight average molecular weight (Mw), molecular weight distribution (Mw / Mn), and differential distribution value difference D of resinM Measurements > Using GPC (gel permeation chromatography), the number average molecular weight (Mn), weight average molecular weight (Mw), molecular weight distribution (Mw / Mn), and differential distribution value difference D of the resin were measured under the following conditions. M was measured. A high-temperature GPC device with a built-in differential refractometer (RI), HLC-8121GPC-HT, manufactured by Tosoh Corporation, was used. Three TSKgel GMHHR-H(20)HT columns manufactured by Tosoh Corporation were connected together and used. Measurements were performed at a column temperature of 140°C, with trichlorobenzene as the eluent at a flow rate of 1.0 ml / min. A calibration curve was prepared using standard polystyrene manufactured by Tosoh Corporation, and the measured molecular weight values were converted to polystyrene values to obtain the number average molecular weight (Mn) and weight average molecular weight (Mw). The molecular weight distribution (Mw / Mn) was obtained using the values of Mw and Mn. In addition, the differential distribution value difference D M was obtained by the following method. First, the time curve (elution curve) of the intensity distribution detected by the RI detector was converted into a distribution curve for the molecular weight M (Log(M)) of the standard polystyrene by using a calibration curve prepared using the above-mentioned standard polystyrene. Next, an integral distribution curve for Log(M) was obtained when the total area of the distribution curve was set to 100%, and then this integral distribution curve was differentiated by Log(M) to obtain a differential distribution curve for Log(M). From this differential distribution curve, the differential distribution values when Log(M)=4.5 and Log(M)=6.0 were read. The difference between the differential distribution value when Log(M)=4.5 and the differential distribution value when Log(M)=6.0 was defined as the differential distribution value difference D M The series of operations leading up to obtaining the differential distribution curve was carried out using the analysis software built into the GPC measuring device used. The results are shown in Table 1.
[0181] <Measurement of heptane insolubles (HI)> Resins A to F were press-molded to 10 mm x 35 mm x 0.3 mm to prepare a measurement sample of about 3 g. Next, about 150 mL of heptane was added and Soxhlet extraction was performed for 8 hours. The heptane insoluble matter was calculated from the sample mass before and after extraction. The results are shown in Table 1.
[0182] <Melt flow rate (MFR) measurement> The melt flow rate (MFR) of each resin in the form of raw resin pellets was measured in accordance with JIS K 7210 condition M using a melt indexer manufactured by Toyo Seiki Co., Ltd. Specifically, a sample weighing 4 g was inserted into a cylinder with a test temperature of 230°C and preheated for 3.5 minutes under a load of 2.16 kg. The weight of the sample extruded from the bottom hole in 30 seconds was then measured to determine the MFR (g / 10 min). The above measurement was repeated three times, and the average value was taken as the measured MFR value. The results are shown in Table 1.
[0183] [Table 1]
[0184] Using the above-mentioned resins, resin films of Examples and Comparative Examples were produced, and their physical properties were evaluated.
[0185] <Preparation of resin film> Example 1 Resin A and resin B were dry blended. The mixing ratio was (resin A):(resin B)=66.7:33.3 by mass ratio. After that, the dry blended resin was used, melted at a resin temperature of 250°C, extruded using a T-die, and solidified by winding it around a metal drum whose surface temperature was kept at 95°C to produce a cast raw sheet. The obtained unstretched cast raw sheet was kept at a temperature of 130°C, passed between rolls with a speed difference, stretched 4.5 times in the flow direction, and immediately cooled to room temperature. Subsequently, the stretched film was introduced into a tenter, stretched 8 times in the width direction at a stretching angle of 9° and a temperature of 158°C, relaxed, heat-set, wound up, and aged in an atmosphere of about 40°C to obtain a biaxially stretched polypropylene film. In this way, a resin film was obtained. The thickness of the obtained resin film was as shown in Table 2 (2.32 μm).
[0186] Example 2 A resin film having a thickness of 4.94 μm was obtained in the same manner as in Example 1, except that Resin C was used and the amount of the resin composition discharged was changed.
[0187] Example 3 A resin film having a thickness of 1.95 μm was obtained in the same manner as in Example 1, except that the amount of the resin composition discharged was changed.
[0188] Example 4 A resin film having a thickness of 2.51 μm was obtained in the same manner as in Example 1, except that the amount of the resin composition discharged was changed.
[0189] Example 5 A resin film having a thickness of 2.07 μm was obtained in the same manner as in Example 1, except that the amount of the resin composition discharged was changed and the stretching ratio in the width direction was changed to 8.1 times.
[0190] Example 6 A resin film having a thickness of 2.55 μm was obtained in the same manner as in Example 1, except that the amount of the resin composition discharged was changed and the stretching ratio in the machine direction was changed to 4.6 times.
[0191] Example 7 A resin film having a thickness of 2.54 μm was obtained in the same manner as in Example 1, except that the amount of the resin composition discharged was changed and the stretching ratio in the machine direction was changed to 4.4 times.
[0192] Example 8 A resin film having a thickness of 2.31 μm was obtained in the same manner as in Example 1, except that the discharge amount of the resin composition was changed and the stretching ratio in the machine direction was changed to 4.3 times.
[0193] (Reference example 3) A resin film having a thickness of 4.90 μm was obtained in the same manner as in Example 1, except that resin C was used, 60,000 ppm of filler (barium titanate, average particle diameter 80 nm (number average value of n = 100 observed with a transmission electron microscope)) was added, and the amount of resin composition discharged was changed.
[0194] Comparative Example 1 A resin film having a thickness of 4.90 μm was obtained in the same manner as in Example 1, except that Resin D was used and the amount of the resin composition discharged was changed.
[0195] Comparative Example 2 A resin film having a thickness of 5.20 μm was obtained in the same manner as in Example 1, except that Resin E was used and the amount of the resin composition discharged was changed.
[0196] Comparative Example 3 A resin film having a thickness of 5.00 μm was obtained in the same manner as in Example 1, except that Resin F was used and the amount of the resin composition discharged was changed.
[0197] Comparative Example 4 A resin film having a thickness of 1.96 μm was obtained in the same manner as in Example 1, except that the amount of the resin composition discharged was changed and the stretching ratio in the width direction was changed to 8.4 times.
[0198] Comparative Example 5 A resin film having a thickness of 2.07 μm was obtained in the same manner as in Example 1, except that the amount of the resin composition discharged was changed and the stretching ratio in the width direction was changed to 8.7 times.
[0199] Comparative Example 6 A resin film having a thickness of 1.96 μm was obtained in the same manner as in Example 1, except that the discharge amount of the resin composition was changed and the stretching ratio in the machine direction was changed to 4.0 times.
[0200] Comparative Example 7 A resin film having a thickness of 2.31 μm was obtained in the same manner as in Example 1, except that the discharge amount of the resin composition was changed and the stretching ratio in the machine direction was changed to 4.2 times.
[0201] The thickness of the resin film was measured by the micrometer method as specified in JIS-C2330, using a paper thickness measuring instrument MEI-11 manufactured by Citizen Seimitsu Co., Ltd.
[0202] <Volume resistivity ρ V23℃ Measurements > The specific procedure for measuring the volume resistivity is described below. Unless otherwise specified, the measurement was performed in accordance with JIS C 2139. First, a jig for measuring volume resistivity (hereinafter, simply referred to as a "jig") was placed in a thermostatic chamber at 23° C. The jig for measuring volume resistivity had the following configuration. A DC power source and a DC ammeter were connected to each electrode of the jig. <Volume resistivity measurement jig> Main electrode (50mm diameter) Counter electrode (diameter 85 mm) A ring-shaped guard electrode (outer diameter 80 mm, inner diameter 70 mm) surrounding the main electrode Each electrode is made of gold-plated copper, and conductive rubber is attached to the surface that comes into contact with the sample. The conductive rubber used is EC-60BL (W300) manufactured by Shin-Etsu Silicone Co., Ltd., and is attached so that the glossy side of the conductive rubber comes into contact with the gold-plated copper.
[0203] Next, the resin films (hereinafter also referred to as samples) of the examples and comparative examples were placed in an environment of 23°C and 50% RH for 24 hours. After that, the samples were set in a jig in a thermostatic chamber. Specifically, the main electrode and the guard electrode were attached to one side of the sample, and the counter electrode was attached to the other side, and the sample and each electrode were attached with a load of 5 kgf. Then, the samples were left to stand for 30 minutes.
[0204] Next, a voltage was applied to the sample so as to give a potential gradient of 200 V / μm.
[0205] After the voltage was applied, the current value was read one minute later, and the volume resistivity was calculated using the following formula: The voltage was applied using a Keithley 2290-10 (DC power source), and the current value was measured using a Keithley 2635B (DC ammeter). Volume resistivity = [(effective electrode area) x (applied voltage)] / [(sample thickness) x (current value)]
[0206] Here, the effective electrode area was calculated by the following formula. (Effective electrode area) = π × [[[(main electrode diameter) + (guard electrode inner diameter)] / 2] / 2] 2
[0207] <Relative permittivity ε r23℃ Measurements > First, a 30 mm diameter formwork was placed on one side of the resin film (hereinafter also referred to as the sample) of the examples and comparative examples, and a conductive paste (Dotite D-500, manufactured by Fujikura Kasei Co., Ltd.) was applied with a brush. After the solvent had sufficiently evaporated and the conductive paste no longer flowed even when the formwork was removed, the formwork was removed and the sample was left for half a day. This formed an electrode. Next, an electrode was formed in the same manner on the other side of the sample, sandwiching the sample and overlapping the previous electrode. As a result, a capacitor with electrodes of 30 mm diameter on each side was obtained.
[0208] To connect the created capacitor to a measuring device, conductors (tin-plated copper wires) were connected to each electrode of the capacitor with conductive paste. At this time, if the conductors were placed opposite each other with the film in between, capacitance would also be formed at the conductor parts, so the conductors were connected at positions as far apart as possible.
[0209] Next, each lead was connected to a measuring device (HIOKI EE Corporation, LCR HiTester 3522-50) to measure the capacitance C of the produced capacitor. The measurement was performed under the following conditions after leaving the capacitor for 30 minutes in a thermostatic chamber set at 23°C. <Measurement conditions> Applied voltage: 1V Measurement frequency: 1KHz
[0210] Then, the relative dielectric constant ε r23℃ The dielectric constant of a vacuum, ε0, is 8.55×10 -12 F / m was used. The results are shown in Table 2. In addition, the product [ρ V23℃ ×ε r23℃ The results are shown in Table 2. In Table 2, notations in the format "E+n" such as "E+16" represent exponents. For example, "E+16" means 10 to the power of +16. The number to the left of the E in "2.44E+16" is a coefficient. For example, "2.44E+16" is 2.44 x 10 16 means... (capacity C)=(ε r23℃ ) × (dielectric constant of vacuum ε0) × [(electrode area) / (resin film thickness)]
[0211] <Volume resistivity ρ V100℃ Measurements > Except for the temperature of the thermostatic chamber being set to 100°C, the volume resistivity ρ V23℃ The volume resistivity ρ of the resin films of the examples and comparative examples was measured in the same manner as in the measurement of V100℃ The results are shown in Table 2.
[0212] <Relative permittivity ε r100℃ Measurements > The temperature of the thermostatic chamber was set to 100°C, but the relative dielectric constant ε r23℃The relative dielectric constant ε of the resin films of the examples and comparative examples was measured in the same manner as in the measurement of r100℃ The results are shown in Table 2. V100℃ ×ε r100℃ The results are shown in Table 2.
[0213] <log 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃ )] calculation> Using the above measurement results, the log 10 [(ρ V23℃ ×ε r23℃ ) / (ρ V100℃ ×ε r100℃ The results are shown in Table 2.
[0214] <Ash content measurement> The resin films of the examples and comparative examples were measured in accordance with JIS-K 7250-1 (2006). Specifically, they were subjected to an ashing treatment at 800°C for 40 minutes, and the resulting ash content (ppm) was measured. The results are shown in Table 2.
[0215] <Measurement of heptane insolubles (HI)> About 3 g of a measurement sample was prepared for the resin films of the examples and comparative examples. Next, about 150 mL of heptane was added and Soxhlet extraction was performed for 8 hours. The heptane insoluble matter was calculated from the sample mass before and after extraction. The results are shown in Table 2.
[0216] <Measurement of molecular weight distribution (Mw / Mn) of resin film> The molecular weight distribution (Mw / Mn) of the resin films of the Examples and Comparative Examples was measured and calculated in the same manner as for Resins A to F. The results were 7.3 for Example 1, 7.7 for Example 2, 7.4 for Example 3, 7.3 for Example 4, 7.3 for Example 5, 7.3 for Example 6, 7.3 for Example 7, 7.3 for Example 8, 7.7 for Reference Example 3, 4.0 for Comparative Example 1, 3.5 for Comparative Example 2, 6.1 for Comparative Example 3, 7.3 for Comparative Example 4, 7.3 for Comparative Example 5, 7.3 for Comparative Example 6, and 7.3 for Comparative Example 7.
[0217] <Measurement of crystallite size of resin film> The crystallite sizes of the resin films according to the examples and comparative examples were measured under the following conditions using an XRD (wide-angle X-ray diffraction) device. Measuring instrument: Rigaku's X-ray diffraction instrument "MiniFlex300" X-ray generation output: 30kV, 10mA X-ray irradiation: Monochromator monochromatized CuKα radiation (wavelength 0.15418 nm) Detector: Scintillation counter Goniometer scan: 2θ / θ coupled scan
[0218] From the obtained data, the half-width of the diffraction reflection peak of the α-crystal (040) plane was calculated using an analytical computer and the integrated powder X-ray analysis software PDXL, which is standard with the device. From the half-width, the crystallite size was calculated using Scherrer's formula (D=K×λ / (β×Cosθ)). The results are shown in Table 2.
[0219] In the Scherrer formula, D is the crystallite size (nm), K is a constant (shape factor: 0.94 is used in this example), λ is the wavelength of the X-ray used (nm), β is the half-width obtained, and θ is the diffraction Bragg angle. 0.15418 nm was used as λ.
[0220] <Measurement of Plane Orientation Coefficient> <Retardation value> First, the retardation (phase difference) values of the resin films according to the examples and comparative examples were measured by the tilt method as described below. Measuring instrument: Retardation measuring device RE-100 manufactured by Otsuka Electronics Co., Ltd. Light source: 550 nm LED light source Measurement method: The angle dependency of retardation value was measured by the following tilt method. The main axes in the in-plane direction of the film were the x-axis and y-axis, and the thickness direction of the film (normal direction to the in-plane direction) was the z-axis. The slow axis in the in-plane direction with a higher refractive index was the x-axis. The retardation values were determined when the film was tilted by 10° from the z-axis in the range of 0° to 50° with the x-axis as the tilt axis. For example, in the sequential stretching method, when the stretch ratio in the TD direction (width direction) is higher than that in the MD direction (flow direction), the TD direction is the slow axis (x-axis) and the MD direction is the y-axis.
[0221] <Birefringence value and plane orientation coefficient ΔP> From the retardation value, as described in the non-patent document "Awaya Yutaka, Introduction to Polarizing Microscopes of Polymer Materials, pp. 105-120, 2001", the plane orientation coefficient ΔP was calculated as follows. First, the measured retardation value R was divided by the thickness d corrected for the tilt angle φ to obtain R / d. The difference between R / d at φ=10°, 20°, 30°, 40°, and 50° and R / d at φ=0° was obtained, and the difference was further divided by sin2r (r: refraction angle) to obtain the birefringence ΔNzy at each φ, and the positive and negative signs were reversed to obtain the birefringence value ΔNyz. The birefringence value ΔNyz was calculated as the average value of ΔNyz at φ=20°, 30°, 40°, and 50°. Next, the retardation value R measured at an inclination angle φ=0° was divided by the thickness d, and the ΔNzy obtained above was divided by the result to calculate the birefringence value ΔNxz. Finally, the birefringence values ΔNyz and ΔNxz were substituted into the formula: ΔP=(ΔNyz+ΔNxz) / 2 to determine ΔP. Note that the refraction angle r value at each inclination angle φ for polypropylene was that described on page 109 of the above-mentioned non-patent document. The results are shown in Table 2.
[0222] <Measurement of melting point and enthalpy of fusion> The melting point and melting enthalpy of the resin film obtained in the examples and comparative examples were obtained by the following procedure using a power compensation type DSC Diamond DSC manufactured by Perkin-Elmer. First, about 5 mg of the resin film was weighed out, packed in an aluminum sample holder, and set in the DSC device. Under nitrogen flow, the temperature was raised from 30°C to 280°C at a rate of 20°C / min (first run), and the melting curve was measured. As a result of the DSC measurement, at least one melting peak was obtained between 100°C and 190°C, and the peak top (apex) temperature of the melting peak curve on the highest temperature side was evaluated as the melting point. In addition, the melting enthalpy was obtained from the results of the first run. The results are shown in Table 2.
[0223] <Measurement of the rate of decrease in insulation resistance (IR) of capacitor elements during life test> Capacitor elements were produced as follows using the resin films obtained in the Examples and Comparative Examples. A metallized film containing a metal film on one side of the resin film was obtained by subjecting the resin film to aluminum deposition with a deposition resistance of 15Ω / □ to a T margin deposition pattern. After slitting to a width of 60 mm, two metallized films were put together, and the deposition film was wound around a φ20 mm core with a winding tension of 250 g using an automatic winder 3KAW-N2 type manufactured by Kaito Seisakusho Co., Ltd., and the number of winding turns was adjusted so that the capacitance of the completed capacitor element was 75 μF (Example 1, Example 3, Example 4, Examples 5 to 8, Comparative Examples 4 to 7) or 50 μF (Example 2, Example 5, Reference Example 3). The wound element was subjected to a heat treatment at 120° C. for 15 hours while pressing, and then zinc metal was sprayed on the element end surface to obtain a flat capacitor. Lead wires were soldered to the end surface of the flat capacitor, and then it was sealed with epoxy resin.
[0224] The insulation resistance value of the obtained capacitor element is evaluated using a super insulation resistance meter DSM8104 manufactured by Hioki E.E. Corporation. The rate of decrease in the insulation resistance value was obtained by the following procedure. After leaving the capacitor element at 23°C for 24 hours, a voltage was applied to the capacitor element with a potential gradient of 250V / μm (500V if the film thickness is 2μm or more), and the insulation resistance value was measured 1 minute after the application. This was the insulation resistance value before the life test.
[0225] Next, the capacitor element was removed from the insulation resistance meter, and a voltage was applied (loaded) to the capacitor element for 1000 hours in a thermostatic chamber at 105°C with a DC high voltage power supply at a potential gradient of DC 280V / μm. Specifically, the DC voltage was determined by the following formula. [DC voltage applied in life test (V)] = 750 × [film thickness (μm)] ÷ εr 100℃ -50 In other words, the applied voltage was 707V in Example 1, 1561V in Example 2, 586V in Example 3, 768V in Example 4, 1717V in Example 5, 625V in Example 6, 782V in Example 7, 778V in Example 8, 703V in Reference Example 3, 1031V in Example 10, 1548V in Comparative Example 1, 1646V in Comparative Example 2, 1580V in Comparative Example 3, 589V in Comparative Example 4, 625V in Comparative Example 5, 589V in Comparative Example 6, and 703V in Comparative Example 7.
[0226] After 1000 hours, the capacitor element was removed and then a discharge resistor was connected to the capacitor element to remove the charge. The capacitor element was then left to stand at 23°C for 24 hours, after which the insulation resistance value of the capacitor element was measured. This is referred to as the insulation resistance value after the life test (hereinafter referred to as "IR 1000 The rate of decrease in insulation resistance was then calculated. The rate of decrease in insulation resistance was evaluated based on the average value of two capacitors. The results are shown in Table 2. [Insulation resistance decrease rate (%)] = [[(insulation resistance value before life test) - (insulation resistance value after life test)] / ((insulation resistance value before life test)] × 100
[0227] <Measurement of capacitance change rate ΔC> The capacitance was measured before and after the life test, and the rate of change in capacitance, ΔC, was calculated using the following formula. The results are shown in Table 2. [Capacitance change rate ΔC (%)] = [[(capacitor capacity before life test) - (capacitor capacity after life test)] / ((capacitor capacity before life test)] × 100 The decrease rate (%) of (C·IR) is also shown in Table 2.
[0228] [Table 2]
[0229] (result) From Table 2, the product [ρ V23℃ ×ε r23℃ ], but 1×10 16 Ω·cm or more, and the product [ρ V100℃ ×ε r100℃ ], but 1×10 14 It can be seen that resin films with a resistance of Ω·cm or more suppress the rate (%) of decrease in insulation resistance (IR) of the capacitor element. In addition, the product [ρ V23℃ ×ε r23℃ ], but 1×10 16 Ω·cm or more, and the product [ρ V100℃ ×ε r100℃ ], but 1×10 14 For resin films with a resistivity of Ω·cm or higher, the rate (%) of decrease in (C·IR) is 50% or less, which indicates that the rate (%) of decrease in (C·IR) is suppressed.
[0230] <Verification of volume resistivity measurement accuracy> It has been verified that the measurement accuracy of the volume resistivity measurement method in the present disclosure is higher than that of Patent Document 1 (WO 2016 / 182003). This will be described below. Reference Example 1 is a test example assuming the method for measuring volume resistivity in Patent Document 1. Reference Example 2 is a test example for confirming how the measurement accuracy changes in comparison with Reference Example 1 when the potential gradient is made higher than that in Reference Example 1.
[0231] (Reference example 1) The jig, DC power source, and DC ammeter for measuring the volume resistivity used in the above-mentioned Examples were prepared. Next, a biaxially oriented polypropylene film having a thickness of 2.3 μm, the same as that of Example 1 of Patent Document 1 (a biaxially oriented polypropylene film manufactured by Oji Holdings Co., Ltd., different from the biaxially oriented polypropylene film of Example 1 described in Patent Document 1), was set in the jig and held at 120° C. for 30 minutes. Thereafter, a voltage of 100 V was applied. In other words, the potential gradient was set to 43 V / μm. As a result, a minute current of 0.1 to 0.5 nA was measured 1 minute after the voltage application. Using these voltage and current results, the volume resistance is calculated assuming the diameter of the electrode area is 10 mm, which is 6.8 × 10 14 The volume resistivity was Ω·cm. This value is the average value of the reproduction test (n=4). The reason for calculating the volume resistivity value assuming that the diameter of the electrode area is 10 mm is to match the electrode area diameter of 10 mm in the volume resistivity measurement method in Patent Document 1. This volume resistivity (6.8×10 14 Ω cm) is 6.5×10 14 The value was close to Ω·cm. Therefore, it is understood that the measurement method of Reference Example 1 is appropriate as a test assuming the measurement method of Patent Document 1. Next, the standard deviation was calculated from the variation in the current measurement values of the reproduction test (n=4). As a result, the standard deviation was 1.2×10 14 The coefficient of variation was calculated to be approximately 18%. The coefficient of variation is a value calculated as follows. (coefficient of variation) = (standard deviation) / (average value) Here, in Patent Document 1, the measurement is performed at 110° C., whereas in Reference Example 1, the measurement is performed at 120° C. The reason for this is as follows. When the test method of Reference Example 1 was used to measure at 110°C, the measured current value was smaller than that of Patent Document 1. Therefore, in order to more accurately reproduce the measurement method of Patent Document 1, the measurement was performed at 120°C in Reference Example 1. The reason why the measured current value is not the same as that of Patent Document 1 when measured at 110°C in the test method of Reference Example 1 is thought to be because the biaxially oriented polypropylene film used in the measurement is not the same as that of Patent Document 1.
[0232] (Reference example 2) As in Reference Example 1, the jig for measuring volume resistivity, a DC power source, and a DC ammeter used in the above-mentioned Examples were prepared. Next, the same biaxially stretched polypropylene film as used in Reference Example 1 was set in the jig and held at 120°C for 30 minutes. After that, in Reference Example 2, a voltage of 200 V was applied. That is, in Reference Example 2, the potential gradient was set to 87 V / μm. The current value was measured in the same manner as in Reference Example 1 except for the potential gradient. As a result, a current of 11 to 12 nA was measured. Using these voltage and current results, the volume resistance is calculated assuming the diameter of the electrode area is 10 mm, and is 5.9 x 10 13 This value is the average value of the replicate test (n=4). Next, the standard deviation was calculated from the variation in the current measurement values of the reproduction test (n=4). As a result, the standard deviation was 3.3×10 12 The coefficient of variation was calculated to be approximately 6%.
[0233] (Consideration) As in Reference Example 1, in the method for measuring volume resistivity in Patent Document 1, the obtained current is at the pA (picoampere) level, and the value is not stable. However, it can be seen that the value becomes stable if the current is measured at the nA (nanoampere) level, as in Reference Example 2. In addition, in Reference Example 2, when the potential gradient is set to 87 V / μm, the value is shown to be more stable compared to Reference Example 1 in which the potential gradient was set to 43 V / μm. Therefore, it can be seen that when the potential gradient is set to 200 V / μm (when this volume resistivity measurement method is used), the value is even more stable compared to the volume resistivity measurement method of Patent Document 1. From the above, it can be seen that the volume resistivity measuring method according to the present disclosure has high accuracy.
Claims
1. A resin film, Contains crystalline thermoplastic resin as the main component, The crystalline thermoplastic resin is a polypropylene resin, The ash content in the resin constituting the resin film is 5 ppm or more and 35 ppm or less, The resin film has a heptane insoluble content of 96% or more and 99.5% or less, The molecular weight distribution of the resin film [(weight average molecular weight Mw) / (number average molecular weight Mn)] is 5 or more and 12 or less, The plane orientation coefficient of the resin film is 0.010 to 0.016, The melting point of the resin film is 170° C. or higher and 176° C. or lower, The melting enthalpy of the resin film is 90 J / g or more and 125 J / g or less, Volume resistivity ρ at 23° C. measured by the following measurement method (1) V23℃ is 4.35 x 10 15 Ω cm or more, Volume resistivity ρ at 100° C. measured by the following measurement method (3) V100℃ is 1.02 x 10 15 A resin film having a resistivity of Ω·cm or more (excluding the case where a nonitol-based nucleating agent is contained and the case where a sorbitol-based nucleating agent is contained). <Measurement method> (1) A voltage is applied in an atmosphere of 23° C. so that the potential gradient is 200 V / μm, and the potential is calculated from the current value after 1 minute has elapsed using the following formula. ρ V23℃ = [(effective electrode area) × (applied voltage)] / [(resin film thickness) × (current value)] (3) A voltage is applied in an atmosphere of 100° C. so that the potential gradient is 200 V / μm, and the voltage is calculated from the current value after 1 minute has elapsed using the following formula. ρ V100℃ = [(effective electrode area) × (applied voltage)] / [(resin film thickness) × (current value)]
2. The resin film according to claim 1, except when it contains talc, when it contains mica, when it contains a phosphate metal salt-based nucleating agent, or when it contains a carboxylate metal salt-based nucleating agent.
3. The volume resistivity ρ at 23° C. measured by the measurement method (1) V23℃ and the relative dielectric constant ε at 23° C. measured by the following measurement method (2) r23℃ The product of [ρ V23℃ ×ε r23℃ ] is 1 x 10 16 Ω cm or more, The relative dielectric constant ε r23℃ is 5.0 or less, The volume resistivity ρ at 100° C. measured by the measurement method (3) V100℃ and the relative dielectric constant ε at 100° C. measured by the following measurement method (4) r100℃ The product of [ρ V100℃ ×ε r100℃ ] is 1 x 10 14 Ω cm or more, The relative dielectric constant ε r100℃ 3. The resin film according to claim 1, wherein the elastic modulus is 5.0 or less. <Measurement method> (2) A conductive paste is applied to both sides of a resin film and dried to form electrodes. Conductive wires are attached to the electrodes using the conductive paste. The capacitance C of the resulting test capacitor is measured in an atmosphere of 23°C, and ε is calculated using the following formula: r23℃ Calculate. (Capacity C) = (ε r23℃ ) × (dielectric constant of vacuum ε 0 ) × [(electrode area) / (resin film thickness)] (4) A conductive paste is applied to both sides of a resin film and dried to form electrodes. Conductive wires are attached to the electrodes using the conductive paste. The capacitance C of the resulting test capacitor is measured in an atmosphere of 100°C, and ε is calculated using the following formula: r100℃ Calculate. (Capacity C) = (ε r100℃ ) × (dielectric constant of vacuum ε 0 ) × [(electrode area) / (resin film thickness)]
4. 4. The resin film according to claim 1, which has a thickness in the range of 0.8 to 6 μm.
5. 5. The resin film according to claim 1, which is for a capacitor.
6. 6. The resin film according to claim 1, which is biaxially stretched.
7. A resin film according to any one of claims 1 to 6, A metal layer-integrated resin film, comprising a metal layer laminated on one or both sides of the resin film.
8. A film capacitor comprising the metal layer-integrated resin film according to claim 7 which is wound, or a plurality of the metal layer-integrated resin films according to claim 7 which are laminated together.
Citation Information
Patent Citations
Combined twooaxissextended polypropylene film for electric insulation
JP1980077567A
High-performance dielectric film improved in heat stability
JP1990150443A
Polypropylene film and capacitor
JP1998156939A
Polypropylene film for capacitor
JP2006229208A
Capacitor film, manufacturing method thereof and capacitor
JP2011187701A